Improved adhesives for absorbent articles - Patents.com

A pressure-sensitive adhesive with tailored rheological properties addresses the challenges of securing absorbent articles to undergarments, ensuring strong initial attachment, retention, and residue-free removal on both cotton and microfiber materials.

JP7614221B2Active Publication Date: 2025-01-15PROCTER & GAMBLE CO
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022562172
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-04-22
Filing Date
2021-04-22
Publication Date
2025-01-15
Estimated Expiration
2041-04-22

AI Technical Summary

Technical Problem

Existing adhesives for securing disposable absorbent articles to clothing, particularly undergarments, face challenges in providing good initial installation, retention in place, and residue-free removal, especially with microfiber underwear, due to issues such as elastic barrier cuffs, consumer application habits, and the influence of cleaning aids.

Method used

The development of a pressure-sensitive adhesive with specific rheological and mechanical properties, including tan δ-1 values of 0.28 to 1.2, storage modulus-1 values less than 85 kPa, tan δ-2 values of 1.9 or less, and storage modulus-2 values greater than 40 kPa, which enhance adhesion to both cotton and microfiber underwear while minimizing residue during removal.

Benefits of technology

The adhesive achieves better attachment, retention, and residue-free removal of absorbent articles on various underwear materials, addressing the limitations of conventional adhesives by ensuring strong initial bonding, staying in place during movement, and leaving no adhesive residue.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007614221000012
    Figure 0007614221000012
  • Figure 0007614221000013
    Figure 0007614221000013
  • Figure 0007614221000014
    Figure 0007614221000014
Patent Text Reader

Abstract

Disposable absorbent articles are described. The disposable absorbent articles include a topsheet that forms at least a portion of the absorbent article's wearer-facing surface, a backsheet that forms at least a portion of the absorbent article's garment-facing surface, an absorbent core disposed between the topsheet and the backsheet, and an adhesive for attaching the disposable absorbent article to an undergarment. The adhesive is disposed on the garment-facing surface. The absorbent article exhibits a peel force of at least 1.0 N, more preferably about 1.1 N, or most preferably about 1.2 N, according to a peel force test, and leaves no residue on the undergarment according to an adhesive residue test.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] SUMMARY OF THE DISPOSABLE ABSORBENT ARTICLE FIELD OF THE DISCLOSURE The present invention relates to an improved adhesive for fastening disposable absorbent articles to garments, particularly underwear. [Background technology]

[0002] Feminine hygiene articles are widely used to absorb menstrual fluid, urine, and other liquid insults. Often, feminine hygiene articles are worn by attaching the article to the user's undergarments. The use of adhesives to secure feminine hygiene articles to personal hygiene undergarments is well known in the art. Commonly, these adhesives are referred to as panty fastening adhesives, position fixing adhesives, or positioning adhesives. For convenience, hereinafter they are collectively referred to as "PFAs."

[0003] PFA plays an important role in ensuring that the wearer is adequately protected and that the user has a good use experience. PFA in feminine hygiene articles essentially has three main responsibilities. First, the PFA should be strong enough to attach the feminine hygiene article to the undergarment during the initial attachment phase. However, this may prove to be more difficult than initially thought. Due to hygiene concerns, users of these articles tend not to apply too much pressure to the feminine hygiene article during initial application, for example believing that less contact with the product will result in less contamination. Less pressure during application may result in poor attachment of the absorbent article during initial application. This problem may be exacerbated by the fact that some feminine hygiene articles, such as adult incontinence pads, include elastic barrier cuffs. The elasticity of the cuffs may act to pull the feminine hygiene article away from the user's undergarment.

[0004] Another problem that can be plagued during initial application of feminine hygiene articles to undergarments is that users tend to stretch their undergarments prior to application to create a flatter surface for adhering the feminine hygiene article. This stretching can cause direct shear on the adhesive. This shear stress on the adhesive can also adversely affect the initial attachment of the feminine hygiene article to the undergarment.

[0005] Second, once affixed to the undergarment, the PFA should keep the feminine hygiene article in place. Users of feminine hygiene articles are typically not stationary the entire time they are wearing the feminine hygiene article. Thus, the PFA must be strong enough to hold the feminine hygiene article in place regardless of the movement of the user and the movement of the user's underwear. Failure to do so may result in increased wrinkling and bunching of the article, which may lead to discomfort for the wearer along with an increased likelihood of leakage.

[0006] Third, the removal of the feminine hygiene article from the undergarment also plays an important role in how the feminine hygiene article is perceived by the user. For example, to address the first and second liabilities above, manufacturers may attempt to utilize higher amounts of PFA in the article. However, such application may also result in negative consumer perception. For example, with higher amounts of PFA, the product may tear or adhesive residue may remain on the undergarment during removal. Adhesive residue still remaining on the undergarment after the article is removed may create a negative image in the user's mind regarding the feminine hygiene article.

[0007] There are additional considerations to keep in mind when attempting to select an appropriate PFA for use in feminine hygiene articles. For example, the material of the underwear can affect how the PFA responds with respect to the three responsibilities above. Two common types of materials used in underwear include cotton (natural) and microfiber (synthetic). While some commercially available PFAs can perform the three functions listed above quite well in cotton underwear, they typically do not perform as well in the context of microfiber underwear. Summary of the Invention [Problem to be solved by the invention]

[0008] Thus, there is a need for a PFA that can provide good initial attachment, stay-in-place protection, and good removal characteristics for a variety of undergarment materials, including cotton, microfiber, etc. The PFA of the present disclosure can alleviate one or more of the problems associated with commercially available PFAs. [Means for solving the problem]

[0009] The PFAs of the present disclosure can provide good attachment of the feminine hygiene article to undergarments, sufficient adhesion during complex wearer movements to provide good stay in place, and good removal characteristics compared to conventional PFAs, particularly for cotton and microfiber undergarments.

[0010] The PFAs of the present disclosure exhibit properties that promote the initial attachment of the PFA, the ability of the PFA to remain in place, and / or the ease of removal of the PFA leaving no or less residue. In a first example, the PFAs of the present disclosure exhibit tan δ-1 values ​​of 0.28 to 1.2, more preferably 0.28 to 1.13, or most preferably 0.28 to 0.51, over a frequency range of 0.01 Hz to 1 Hz at 37° C., according to the Frequency Sweep-Oscillatory Rheometry Test Method. The PFAs of the present disclosure also exhibit storage modulus-1 values ​​of less than 85 kPa, more preferably 74 kPa or less, or most preferably 57 kPa or less, over a frequency range of 0.01 to 1 Hz at 37° C., according to the Frequency Sweep-Oscillatory Rheometry Test Method. The PFAs of the present disclosure exhibit tan δ-2 values ​​of 1.9 or less, more preferably 1.8 or less, or most preferably 1.38 or less, over a frequency range of 50 to 100 Hz at 37° C., according to the Frequency Sweep-Oscillatory Rheometry Test Method. And finally, the PFAs of the present disclosure also exhibit a Storage Modulus-2 value greater than 40 kPa, more preferably greater than or equal to 73 kPa, or most preferably greater than or equal to 146 kPa, at 50 Hz to 100 Hz at 37° C., according to a Frequency Sweep-Oscillatory Rheometry test method, where the Storage Modulus-2 value is greater than the Storage Modulus-1 value.

[0011] In a second example, a method of using an adhesive for an absorbent article is disclosed, the method comprising formulating an adhesive exhibiting the properties disclosed in the first example above.

[0012] In a third example, a method of manufacturing an absorbent article is disclosed, the method comprising the steps of obtaining a topsheet material, obtaining an absorbent material, obtaining a backsheet material, and obtaining an adhesive exhibiting the properties disclosed in the first example above.

[0013] In a fourth example, a method of manufacturing an absorbent article is disclosed, the method comprising the steps of obtaining a topsheet material, obtaining an absorbent material, and obtaining a backsheet material, the backsheet material including an adhesive disposed on a garment-facing surface of the backsheet and exhibiting the properties disclosed in the first example above.

[0014] In a fifth example, a disposable absorbent article is disclosed. The disposable absorbent article comprises a topsheet forming at least a portion of the wearer-facing surface of the absorbent article, a backsheet forming at least a portion of the garment-facing surface of the absorbent article, an absorbent core disposed between the topsheet and the backsheet, and an adhesive for attaching the disposable absorbent article to an undergarment, the adhesive being disposed on the garment-facing surface. The absorbent article exhibits a peel force of at least 1.0 N, more preferably about 1.1 N, or most preferably about 1.2 N according to a peel force test, and leaves no residue on the undergarment according to an adhesive residue test. [Brief description of the drawings]

[0015] [Figure 1A] 1 is a graph showing storage modulus-1 values ​​of adhesive samples 1 to 4 according to the present disclosure. [Figure 1B] 1 is a graph showing the storage modulus-1 values ​​of adhesive samples 5 to 9 that do not meet the criteria described in this disclosure. [Figure 2A] 1 is a graph showing tan δ-1 values ​​of adhesive samples 1 to 4 according to the present disclosure. [Figure 2B] 1 is a graph showing the tan δ-1 values ​​of adhesive samples 5 to 9 that do not meet the criteria described in the present disclosure. [Figure 3A] 1 is a graph showing storage modulus-2 values ​​of adhesive samples 1 to 4 according to the present disclosure. [Figure 3B] 1 is a graph showing the storage modulus-2 values ​​of adhesive samples 5 to 9 that do not meet the criteria described in the present disclosure. [Figure 4A] 1 is a graph showing tan δ-2 values ​​of adhesive samples 1 to 4 according to the present disclosure. [Figure 4B] 1 is a graph showing the tan δ-2 values ​​of adhesive samples 5 to 9 that do not meet the criteria described in this disclosure. [Figure 5A] 1 is a graph showing the tan δ-1 values ​​of Adhesive Sample 1 at two different temperatures, namely 25° C. and 37° C. [Figure 5B]1 is a graph showing the tan δ-1 values ​​of adhesive sample 2 at two different temperatures, namely 25° C. and 37° C. [Figure 5C] 1 is a graph showing the tan δ-1 values ​​of adhesive sample 3 at two different temperatures, namely 25° C. and 37° C. [Figure 5D] 1 is a graph showing the tan δ-1 values ​​of Adhesive Sample 4 at two different temperatures, namely 25° C. and 37° C. [Figure 6A] 1 is a graph showing the tan δ-1 values ​​of Adhesive Sample 5 at two different temperatures, namely 25° C. and 37° C. [Figure 6B] 1 is a graph showing the tan δ-1 values ​​of Adhesive Sample 6 at two different temperatures, namely 25° C. and 37° C. [Figure 6C] 1 is a graph showing the tan δ-1 values ​​of Adhesive Sample 7 at two different temperatures, namely 25° C. and 37° C. [Figure 6D] 1 is a graph showing the tan δ-1 values ​​of adhesive sample 8 at two different temperatures, namely 25° C. and 37° C. [Figure 6E] 1 is a graph showing the tan δ-1 values ​​of adhesive sample 9 at two different temperatures, namely 25° C. and 37° C. [Figure 7A] 1 is a graph showing the tan δ-1 values ​​of Adhesive Sample 1 at two different temperatures, namely 25° C. and 37° C. [Figure 7B] 1 is a graph showing the tan δ-1 values ​​of adhesive sample 2 at two different temperatures, namely 25° C. and 37° C. [Figure 7C] 1 is a graph showing the tan δ-1 values ​​of adhesive sample 3 at two different temperatures, namely 25° C. and 37° C. [Figure 7D] 1 is a graph showing the tan δ-1 values ​​of Adhesive Sample 4 at two different temperatures, namely 25° C. and 37° C. [Figure 8A] 1 is a graph showing the tan δ-1 values ​​of Adhesive Sample 5 at two different temperatures, namely 25° C. and 37° C. [Figure 8B] 1 is a graph showing the tan δ-1 values ​​of Adhesive Sample 6 at two different temperatures, namely 25° C. and 37° C. [Figure 8C] 1 is a graph showing the tan δ-1 values ​​of Adhesive Sample 7 at two different temperatures, namely 25° C. and 37° C. [Figure 8D] 1 is a graph showing the tan δ-1 values ​​of adhesive sample 8 at two different temperatures, namely 25° C. and 37° C. [Figure 8E] 1 is a graph showing the tan δ-1 values ​​of adhesive sample 9 at two different temperatures, namely 25° C. and 37° C. [Figure 9A] 1 is a graph showing the bonding compliance values ​​of adhesives for Samples 1 to 9. [Figure 9B] 1 is a graph showing the peel compliance values ​​of the adhesives of Samples 1 to 9. [Figure 10A] 1 is a micro-CT image showing the adhesive of Sample 1 bonded to a portion of a microfiber underwear. [Figure 10B] 1 is a micro-CT image showing the adhesive of Sample 6 bonded to a portion of a microfiber underwear. [Figure 11A] 1 is a SEM image showing a cross section of the adhesive of Sample 7 bonded to a portion of a microfiber undergarment. [Figure 11B] 1 is a SEM image showing a cross section of the adhesive of Sample 7 bonded to a portion of a microfiber undergarment. [Figure 11C] 1 is a SEM image showing a cross section of the adhesive of Sample 7 bonded to a portion of a microfiber undergarment. [Figure 11D] 1 is a SEM image showing a cross section of the adhesive of Sample 7 bonded to a portion of a microfiber undergarment. [Figure 12A] 1 is a SEM image showing a cross section of the adhesive of Sample 4 bonded to a portion of a microfiber undergarment. [Figure 12B] 1 is a SEM image showing a cross section of the adhesive of Sample 4 bonded to a portion of a microfiber undergarment. [Figure 12C] 1 is a SEM image showing a cross section of the adhesive of Sample 4 bonded to a portion of a microfiber undergarment. [Figure 12D]1 is a SEM image showing a cross section of the adhesive of Sample 4 bonded to a portion of a microfiber undergarment. [Figure 13] 1 is a schematic diagram of an absorbent article constructed in accordance with the present disclosure. [Figure 14] 1 is a schematic diagram of another absorbent article constructed in accordance with the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] As used herein, "absorbent article" refers to articles that absorb and contain liquids or exudates exuded from the body, such as bodily fluids, and is intended to include sanitary napkins, panty liners, and incontinence pads (and other articles worn in the crotch area of ​​clothing), as well as additional articles that are intended to be placed within and adhered to the user's undergarments.

[0017] "Longitudinal" with respect to an absorbent article refers to the front-to-back or back-to-front direction of the article from the wearer's perspective.

[0018] "Lateral" with respect to an absorbent article refers to the direction perpendicular to the longitudinal direction and from side to side of the article, as viewed from the wearer's perspective.

[0019] For a component of a wearable absorbent article that is composed of multiple components, the "wearer-facing" component is the component that is disposed closest to the wearer's skin when the article is worn, and the "garment-facing" component is the component that is disposed furthest from the wearer's skin. For two opposing major surfaces of a web, sheet or batt component of a wearable absorbent article, the "wearer-facing" surface is the surface that faces the wearer's skin when the article is worn, and the opposite "outer-facing" surface is the surface that faces away from the wearer's skin.

[0020] As mentioned above, there are many considerations related to the performance of PFA. For example, as mentioned above, the material of the underwear can greatly affect the performance of PFA. One material that is widely used by consumers is underwear made of microfiber material. Microfiber is one of the major recent developments in the textile industry. These fibers traditionally have a thickness of less than 1 denier. Microfibers have found applications especially in the clothing industry, where they are used to form textiles with unique physical and mechanical properties. Microfibers are thinner than silk and have very good strength, uniformity, and processing properties, so that microfibers can provide the wearer with a luxurious look and feel.

[0021] Also, as mentioned above, PFA that works well on cotton underwear may not work as well on microfiber underwear, which can be understood in terms of the surface properties of the underwear / adhesive system and the relative stretch mismatch between the underwear and the pad.

[0022] This problem with attaching absorbent articles to underwear, especially microfiber materials, is a widespread problem. Adhesive failure, specifically PFA, is one of the major complaints that consumers make about the use of absorbent articles. And, as demonstrated in the art, for example by US Patent Application Publication Nos. 2005 / 0256481 and 2015 / 0038936(A1), the need for adhesives suitable for use with microfibers has existed for over a decade. However, for the various underwear materials available to consumers today, there is no commercially available PFA that can meet the three above-mentioned responsibilities (i.e., initial attachment, staying in place, and removal without leaving residue).

[0023] To further complicate matters, in addition to the problems identified above, the inventors have further discovered that the outcome of PFA attachment is strongly influenced by the application habits of the consumer. All PFAs require initial pressure to flow the adhesive and achieve a bond between the article and the undergarment. Also, as mentioned above, consumers tend to avoid touching the product during application due to hygiene concerns, and therefore apply very little pressure only to very limited areas of the product (usually the front and wings). Thus, consumer application habits tend to be poor in terms of creating the essential initial bond with the undergarment.

[0024] Furthermore, without wishing to be bound by theory, it is believed that washing habits may affect PFA performance as well. Since the introduction of washing and drying aids such as fabric softeners and dryer sheets, it is believed that PFA performance has been affected. It is further believed that the decrease in PFA performance may be adversely affected by these washing and drying aids, which deposit hydrophobic actives (e.g., alkyl ester quaternary ammonium and fatty acids) in fabric softeners onto the surface of clothing.

[0025] It is further believed that the number and frequency of washing can affect the ability of the PFA to attach to the undergarment, regardless of the undergarment material. This is believed to be due to increased surface "fuzzing" or loosening of fibers by the garment with increased washing. This increased "fuzzing" can help provide additional anchoring points for the adhesive and create a stronger bond. However, the increased number of anchoring points can adversely affect removal of the article (and its PFA) from the undergarment, potentially leading to an increase in residual PFA being left behind on the undergarment.

[0026] Regardless of the complexity of the problem that needs to be solved, the inventors have surprisingly found several criteria that influence the performance of PFA, specifically how PFA performs with respect to microfiber and / or cotton underwear. The PFA of the present disclosure can be superior to conventional PFA in one or more of the three main responsibilities of PFA with respect to absorbent articles. Moreover, the PFA of the present disclosure is an improvement over commercially available PFA.

[0027] The rheological and mechanical behavior of an adhesive plays an important role in its performance as a PFA. One criterion related to the rheology of PFA is the attenuation coefficient. To address the aforementioned requirements for initial placement, staying in place, and removal, the attenuation coefficient can be measured at least in two different frequency ranges. This relates to different time scales that are involved in different phases of the adhesive's life. During application and subsequent initial wear, the PFA can flow for a very long time and be in intimate contact with the garment fibers, enhancing adhesive strength. This time scale is typically on the order of 1 second to 100 seconds or more, for which the attenuation coefficient (tan δ-1) can be from about 0.01 Hz (= 1 / 100 seconds) to about 1 Hz = (1 / 1 second) for the initial placement and staying in place criteria. As mentioned above, the measurement of tan δ-1 can be important for the initial placement as well as the staying in place criteria. Tan δ-1 is measured as described herein at frequencies of 0.01 to 1 Hz at 37°C. 37°C is believed to more closely mimic body temperature and the conditions under which PFA would perform.

[0028] In the case of the PFA of the present disclosure, the PFA can be configured to exhibit a tan δ-1 value that allows the PFA to attach to the macro surface structure of the undergarment fabric. Without wishing to be bound by theory, it is believed that a high tan δ-1 value (coupled with a low storage modulus-1 (G'1) value as disclosed herein) leads to a high compliance value. The higher the compliance value, the more conformable and intimately contacted the adhesive is with the undergarment surface, resulting in a stronger bond of the PFA to the undergarment. This compliance value is described in more detail below. It is believed that the ability to adhere to a greater number of fibers of the undergarment, especially during the initial application, plays an important role in the initial successful attachment of the absorbent article to the undergarment, regardless of the material (e.g., cotton, microfiber, etc.).

[0029] The PFAs of the present disclosure, when measured over a frequency range of 0.01 Hz to 1 Hz at 37°C according to the Frequency Sweep-Oscillatory Rheometry test method described herein, can exhibit tan δ-1 values ​​of 0.28 to 1.2, more preferably 0.28 to 1.13, or most preferably 0.28 to 0.51, specifically all values ​​within this range and any range created thereby. The PFAs of the present disclosure, at 0.01 Hz at 37°C, can exhibit tan δ-1 values ​​of 0.28 to 0.9, specifically all values ​​within this range and any range created thereby. It should be noted that the PFAs of the present disclosure can exhibit the above tan δ-1 values ​​throughout the range of 0.01 Hz to 1 Hz. Thus, at 0.01 Hz and 1 Hz, the tan δ-1 values ​​can be 0.28 to 1.2, specifically all values ​​within this range and any range created thereby.

[0030] As explained above, during application of the absorbent article to the user's undergarments and subsequent initial wear, the PFA can flow for an extended period of time and come into intimate contact with the fibers of the undergarment. However, within the specified frequency range, there is no set time for the article to be applied to the undergarment, in fact quite the opposite. From a time perspective, application of the article to the undergarment is highly variable. Also, as noted above, initial application is important to establish good adhesion between the PFA and the undergarment.

[0031] As mentioned above, when an absorbent article is applied to an undergarment, the amount of time given to the PFA to bond to the undergarment varies widely. Surprisingly, the inventors have found that the relaxation time of the PFA can be important when the usefulness of bonding the PFA to the undergarment is desired. Furthermore, the inventors have found that the temperature at which the relaxation time is measured can affect the measurement results. For example, the relaxation time of a PFA measured at 25°C can be substantially longer than the relaxation time of the same PFA measured at 37°C.

[0032] During application of the absorbent article, it is believed that there is a mixture of these temperatures, or a mixture of temperatures between these temperatures. For example, when the absorbent article is first applied to the undergarment, the PFA and absorbent article are likely to be fairly close to room temperature, i.e., 25°C. However, when the undergarment is put back on, the absorbent article and PFA begin to increase in temperature. Eventually, the absorbent article and PFA reach a steady state at a temperature near body temperature, i.e., a few degrees / few degrees below 37°C. At elevated temperatures, the relaxation time of the PFA may be substantially less than the relaxation time measured at 25°C. The PFA of the present disclosure may have a relaxation time at 37°C of 100 seconds or less, more preferably 30 seconds or less, or most preferably 20 seconds or less, but may specifically take all values ​​within this range and any ranges created thereby.

[0033] The relaxation times of the sample adhesives disclosed in Table 1 were calculated according to the following formula:

[0034]

number

[0035] As mentioned above, the damping coefficient of PFA is important to determine the behavior of PFA with respect to initial attachment and remaining in place. However, the inventors have also found that the damping coefficient at higher frequencies may also be important when removing the product from the undergarment, as consumers typically remove the absorbent article in less than one second. Assuming that the pad can be removed in 0.01 seconds or more, the tan δ-2 value can be measured at 50-100 Hz at 37°C for removal. As a significant concern that parallels the desirable attributes of PFA in the description of tan δ-1, the PFA of the present disclosure is cohesive enough to be peeled off with the adhesive from the panty and minimize the possibility of leaving residue on the undergarment after article removal. As mentioned above, PFA residue still remaining after removal of the absorbent article can create a negative image of the absorbent article brand in the user's mind.

[0036] The PFAs of the present disclosure, when measured according to the Frequency Sweep-Oscillatory Rheometry test method disclosed herein, can exhibit tan δ-2 values ​​of 1.9 or less, more preferably 1.8 or less, or most preferably 1.38 or less, over a frequency range of 50-100 Hz at 37°C, and specifically all values ​​within this range and any ranges created thereby. For example, these PFAs of the present disclosure can exhibit tan δ-2 values ​​of 0.25-1.9, more preferably 0.25-1.8, or most preferably about 0.28 to about 1.38, over a frequency range of 50-100 Hz at 37°C, and specifically all values ​​within this range and any ranges created thereby. It is noteworthy that the PFAs of the present disclosure exhibit the above tan δ-2 values ​​over the entire range of 50 Hz to 100 Hz. Thus, at 50 Hz and 100 Hz, the tan δ-2 value can be 1.9 or less, more preferably 1.8 or less, or most preferably 1.38 or less, but can specifically be any value within this range and any range created thereby.

[0037] Another rheological criterion is a measure of the elastic stiffness of the PFA. This metric is called storage modulus. In order for the PFA to stick to a surface, the PFA of the present disclosure may have a "soft" property so that the adhesive can conform to any discontinuities in the surface of the fabric of the undergarment to which the absorbent article is attached. This "soft" property may affect not only the initial application, but also the aspect of the absorbent article remaining in place and its peelability.

[0038] Similar to the damping coefficient, the storage modulus (G') of PFA in the frequency range of 0.01 Hz to 1 Hz can be indicative of the "softness" of the adhesive and its ability to conform to the substrate and create adhesion - referred to as storage modulus-1. However, the storage modulus of the adhesive in the frequency range of 50 Hz to 100 Hz can be an important contributor to both the adhesive strength and cohesion of the adhesive upon removal of the article - referred to as storage modulus-2. This adhesive strength and cohesion can minimize the possibility of leaving residue on the undergarment after removal of the absorbent article. And similar to the damping coefficient in two different frequency ranges, the criteria of storage modulus-1 and storage modulus-2 can be conflicting concerns. Storage modulus-1 and storage modulus-2 can be difficult to achieve in a single PFA, with the former being low to provide better adhesion during application and the latter being high to provide adhesive cohesion.

[0039] The PFAs of the present disclosure may exhibit a storage modulus-1 value of less than 85 kPa, more preferably 74 kPa or less, or most preferably 57 kPa or less, at a frequency of 0.01 to 1 Hz at 37°C, but may specifically take any value within this range and any range created thereby. For example, these PFAs may exhibit a storage modulus-1 value of 1 kPa to 84 kPa, more preferably 3 kPa to 74 kPa, or most preferably 12 kPa to 57 kPa, at a frequency of 0.01 to 1 Hz at 37°C, but may specifically take any value within this range and any range created thereby. In conjunction with or independent of the foregoing, the PFAs of the present disclosure may exhibit a storage modulus-1 value of 5 kPa to 84 kPa, more preferably 5 kPa to 80 kPa, and most preferably 5 kPa to 74 kPa, at 1 Hz at 37°C, but may specifically take any value within this range and any range created thereby. In conjunction with or independently of the foregoing, the PFAs of the present disclosure may exhibit a storage modulus-1 value at 0.01 Hz at 37° C. of from 1 kPa to 50 kPa, more preferably from 1 kPa to 40 kPa, or most preferably from 1 kPa to 30 kPa, but specifically may have any value within this range and any range created thereby.

[0040] With respect to the storage modulus-2 value, the PFA of the present disclosure may exhibit a storage modulus-2 value of 40 kPa or more, more preferably 73 kPa or more, or most preferably 146 kPa or more, at 37°C and 50-100 Hz according to the frequency sweep-oscillatory rheometry test method disclosed herein, but specifically may take all values ​​within this range and any range created thereby. As an example, the PFA of the present disclosure may exhibit a storage modulus-2 value of 40-300 kPa, more preferably 73 kPa-300 kPa, or most preferably 146 kPa-300 kPa, but specifically may take all values ​​within this range and any range created thereby. However, the storage modulus must be considered in its entirety as a continuous, monotonically increasing function of frequency. This means that the storage modulus-2 value cannot be less than the storage modulus-1 value.

[0041] It is believed that by appropriately selecting the tan δ-1 and storage modulus-1 values, the PFA of the present disclosure can reduce the negative effects caused by the previously mentioned consumer application habits. As we know, consumers tend not to apply excessive pressure to the article, except for the wings (if available), to avoid the problem of perceived contamination. Conventional pressure-sensitive adhesives require a great deal of interaction from the consumer in the way of applying pressure to the article to form a bond to the underwear. In contrast, it is believed that the PFA of the present disclosure can form a sufficient bond even with the current application habits of consumers by appropriately selecting the tan δ-1 and storage modulus-1 values ​​described herein. Therefore, it is possible to address the current application habits of users by appropriately selecting the tan δ-1 and storage modulus-1 values ​​described herein.

[0042] The inventors further discovered that due to the initial attachment and remaining in place features, the PFA of the present disclosure can exhibit a joint compliance value -J1. The joint compliance value characterizes the relationship between tan δ-1 and storage modulus-1. The equation for joint compliance is shown below:

[0043]

number

[0044] Without wishing to be bound by theory, it is believed that the bond compliance value indicates how well the adhesive can flow and bond to the structure it is required to adhere to. In the case of cotton and / or microfiber underwear, the bond compliance value indicates how well the adhesive will flow and adhere to the macro-structure (fiber level) of the underwear. In the case of the PFAs of the present disclosure, these PFAs have a 7.5 mm 2 / N~950mm 2 / N, more preferably 8.5mm 2 / N~approx. 600mm 2 / N, or most preferably about 9 mm 2 / N~approx. 321mm 2 The joint compliance value may be any value within this range and any range created thereby.

[0045] Similarly, with regard to removal function, the inventors have found that the PFA of the present disclosure can exhibit a peel compliance value -J2. The peel compliance value utilizes the relationship between tan δ2 and storage modulus2.

[0046]

number

[0047] Without wishing to be bound by theory, it is believed that the peel compliance value indicates the cohesive strength of the adhesive. Thus, it is believed that the peel compliance value can indicate whether the adhesive will leave a residue on the undergarment upon removal of the article from the undergarment. In the case of the PFAs of the present disclosure, these PFAs have a peel compliance value of 0.3 mm. 2 / N~255.6mm 2 / N, more preferably about 1.5 mm 2 / N~approx. 150mm 2 / N, or most preferably about 2.2 mm 2 / N~approx. 13.2mm 2 1 / N, but may specifically take any value within this range and any range created thereby.

[0048] Another mechanical parameter that may affect how PFA performs is its modulus of elasticity or Young's modulus. As is known, users often stretch the feminine hygiene article before attaching it to the undergarment. This stretching of the undergarment may cause stresses in the PFA of the feminine hygiene article. It is believed that PFA with a higher modulus of elasticity is better able to handle these forces. With this in mind, the PFA of the present disclosure may have a modulus of elasticity between 0.1 MPa and 1.5 MPa, more preferably between 0.12 MPa and 1.2 MPa, and most preferably between 0.14 MPa and 1 MPa, when measured at an elongation rate of 0.11 / sec and an ambient temperature of 23°C ± 2°C.

[0049] With respect to peeling, the inventors have also found that the yield stress of the PFA can provide additional information regarding whether the PFA leaves residue on the undergarment during removal. The PFA of the present disclosure can exhibit a yield stress of 32 kPa or more, more preferably 40 kPa or more, or most preferably 50 kPa or more, when measured at 37° C. according to the Yield Stress Elongation Test Method described herein, but can specifically take any value within this range and any range created thereby. For example, in some specific configurations, the PFA of the present disclosure can exhibit a yield stress of 32 kPa to about 100 kPa, more preferably about 40 kPa to about 100 kPa, or most preferably about 50 kPa to about 100 kPa, but can specifically take any value within this range and any range created thereby.

[0050] Without wishing to be bound by theory, it is believed that the PFA is stressed during its removal. As is known, during use, the PFA creates an adhesive interface between the backsheet of the absorbent article and the PFA as well as an adhesive interface between the PFA and the undergarment. If the adhesive has a yield stress of less than about 32 kPa, the adhesive interface will resist removal and instead the PFA will fail internally. This internal failure may lead to increased residue remaining in the undergarment. However, if the PFA has a yield stress of more than 32 kPa, it is believed that the adhesive has sufficient strength to cause the PFA to break the adhesive interface between the PFA and the undergarment, thereby reducing the likelihood that PFA residue will remain in the undergarment.

[0051] The above criteria are believed to be the most influential in terms of whether an adhesive can be successfully attached to underwear of various materials. However, the inventors have surprisingly found that adhesives that meet the criteria mentioned herein can also exhibit lower surface energy values ​​with microfiber and cotton materials than adhesives that do not perform well. The inventors have also found that PFAs that perform well can exhibit surface polarity that is a lower percentage of the total surface energy than adhesives that do not perform well. It is believed that surface energy can affect the initial attachment of PFA to underwear and the sustained adhesion of PFA to underwear. This is particularly true in cases where, for example, a washing / drying aid is utilized by the consumer, as described above, before the hydrophobic actives (e.g., alkyl ester quaternary ammonium and fatty acid) in the fabric softener are deposited on the surface of the garment.

[0052] The PFAs of the present disclosure may exhibit a surface energy of less than 25 millijoules per square meter when measured according to the total surface energy method disclosed herein to accommodate good adhesion to both cotton and microfiber underwear, but may specifically include all values ​​within this range and any ranges created thereby. For example, these PFAs of the present disclosure may exhibit a surface energy of less than 10 mJ / m 2 ~24mJ / m 2 , more preferably 12.5 mJ / m 2 ~24mJ / m 2 , or most preferably 15 mJ to 24 mJ / m 2 may refer to a surface energy of, but may specifically refer to any value within this range and any range created thereby.

[0053] The inventors have also found that for adhesives that meet the above criteria, the polar component of the surface energy also falls within a certain range. That is, the PFA of the present disclosure may exhibit a polar component of less than 10%. For example, the polar component may be 1%-9%, more preferably 2%-9%, or most preferably 3%-9%, but may specifically be any value within this range and any range created thereby.

[0054] Each of the above criteria has been measured on a large number of adhesives, and data showing these measurements is provided herein.

[0055] composition Furthermore, the PFA of the present disclosure may comprise any suitable chemical structure. (For the avoidance of doubt) the PFA of the present disclosure is intended to mean a pressure-sensitive adhesive that is inherently tacky, viscoelastic, and cohesive in its normal dry state. In its simplest form, the PFA of the present disclosure may comprise a polymer or polymer blend and a tackifier.

[0056] Some exemplary PFAs can include any number of polymeric backbones. For example, the PFAs of the present disclosure can include a polymeric backbone that includes at least one of a thermoplastic polyurethane (TPU) silicone, an acrylate ester / vinyl pyrrolidone copolymer, a dimethyl silicone polymer, or an acrylate polymer.

[0057] The PFA of the present disclosure may comprise a mixture of 60-90% by weight of pure rubbery copolymers (C3-C12 alkyl esters) and 10-40% by weight of polar components. Some suitable examples of (C3-C12 alkyl esters) include isooctyl acrylate, 2-ethyl-hexyl acrylate, and n-butyl acrylate. Some suitable examples of polar components include acrylic acid, methacrylic acid, ethylene vinyl acetate, N-vinyl pyrrolidone, and styrene block copolymers.

[0058] In one specific example, the PFA of the present disclosure comprises a polymer backbone of ethylene vinyl acetate and styrene block copolymer. These PFAs may utilize one or more tackifiers or blends thereof. The advantages of using a tackifier include (i) increasing the open time of the adhesive (which generally allows for better transfer to the second substrate in the lamination process, especially when the process open time (defined as the distance between the applicator and the combination point divided by the line speed) is short), and (ii) allowing the desired polarity of the adhesive to be achieved (which contributes to increasing the bond strength to more polymeric substrates (e.g., polyester fibers), especially in bonds where optimal fiber entanglement is difficult to achieve). In the case of the PFA of the present disclosure, the inventors have surprisingly found that minimizing the amount of tackifier has a net positive effect to achieve better adhesion for underwear that exhibit a dispersive component significantly higher than the polar component of the surface energy, either as a result of washing habits, or in the case of most microfiber manufacturers, due to their surface finishing treatment.

[0059] The tackifier preferably has a molecular weight (Mw) of less than 6,000 Da and a Tg (glass transition temperature) below or slightly above room temperature. A Tg significantly above room temperature would result in an adhesive that does not meet the storage modulus values ​​referenced herein.

[0060] Suitable types of tackifiers include, for example, aromatic, aliphatic, and cycloaliphatic hydrocarbon resins, mixed aromatic and aliphatic modified hydrocarbon resins, aromatic modified aliphatic hydrocarbon resins; terpenes, modified terpenes; natural rosin, modified rosin, rosin esters, and combinations thereof.

[0061] Suitable commercially available tackifiers include those sold under the tradename ESCOREZ series, e.g., ESCOREZ 5300, ESCOREZ 5400, and ESCOREZ 5600, from Exxon Mobil Chemical Company, Houston, Texas, and those sold under the tradename EASTOTAC series, e.g., EASTOTAC H-100R and EASTOTAC H-100L, from Eastman Chemical Company, Kingsport, Tenn.

[0062] In another specific example, the PFA according to the present disclosure includes an acylate polymer-based backbone. These adhesives may include 80-100% by weight isooctyl acrylate and 0-20% by weight acrylic acid. Additionally, the acrylic pressure-sensitive adhesives may be self-adhesive or tackified. Useful tackifiers (less than 2% by weight) for acrylic adhesives include rosin esters such as FORAL™ 85 or aromatic resins such as PICCOTEX™ LC-55WKm, both available from Hercules, Inc. (Wilmington, DL), or other aliphatic resins such as ESCOREZ™ 1310LC, available from Exxon Chemical Co., (Houston, TX).

[0063] With respect to the polar component, for example, thermoplastic elastomeric materials that are particularly useful in the present invention include, for example, styrene-isoprene block copolymers such as KRATON™ D1107P, or linear styrene-(ethylene-butylene) block copolymers such as KRATON™ G1657, or linear styrene-(ethylene-propylene) block copolymers such as KRATON™ G1657X, and styrene-butadiene star block copolymers such as KRATON™ D1118X, all available from Shell Chemical Co, (Houston, TX).

[0064] These thermoplastic elastomer or elastomeric materials may also be modified with tackifying resins or plasticizers to reduce their melt viscosity and promote the formation of fine dispersions, preferably with a minimum phase dimension of less than about 20 micrometers, when blended with acrylic pressure-sensitive adhesives. Tackifying resins or plasticizers useful with elastomeric or thermoplastic elastomer materials are preferably miscible at the molecular level, i.e., soluble in any or all of the polymer segments of the elastomeric or thermoplastic elastomer materials. Tackifying resins, if present, should be kept at low concentrations, as previously mentioned, for the reason that they reduce the polar fraction of the adhesive's surface energy, and may comprise from about 5 to 600 parts by weight, more typically up to about 500 parts by weight, per 100 parts by weight of elastomeric or thermoplastic elastomer materials. Examples of tackifiers suitable for the PFAs of the present disclosure include, but are not limited to, liquid rubber, hydrocarbon resins, rosins, natural resins such as dimerized or hydrogenated balsams and esterified abietic acid, polyterpenes, terpene phenols, phenol-formaldehyde resins, and rosin esters. Plasticizers are also important components in the PFAs of the present disclosure, typically present at 5-10% by weight. Examples of plasticizers include, but are not limited to, polybutene, paraffin oil, petrolatum, and certain phthalates with long aliphatic side chains, such as ditridecyl phthalate.

[0065] The adhesives of the present disclosure may also optionally include additives, such as, for example, one or more antioxidants, UV stabilizers, gloss agents, colorants, fragrances, odor control actives, etc. The adhesives may include less than 5% by weight of such additives. Any antioxidant known to one of ordinary skill in the art may be used in the adhesives of the present disclosure.

[0066] sample Several samples were obtained and tested against the criteria disclosed herein and others.

[0067] Samples 1-3 were polyacrylate adhesives and each had good adhesion to microfiber underwear.

[0068] Sample 4 was a mixture of ethylene vinyl acetate and styrene block copolymer adhesives and had good adhesion to the microfiber underwear.

[0069] Samples 5-6 were polyurethane elastomer based adhesives and each did not provide sufficient adhesion to the microfiber undergarments.

[0070] Samples 7-8 were styrene block copolymer based adhesives and each did not provide sufficient adhesion to the microfiber undergarments.

[0071] Sample 9 was a styrene block copolymer based adhesive.

[0072] Samples 1-2 utilized adhesives that are commercially available as general purpose adhesives. Sample 1 is available under the trade name "Voxmude Double Sided Clear Adhesive Gel Grip Tape." This tape is advertised as being suitable for use on a variety of wall and floor surfaces.

[0073] Sample 2 is available from Anothera under the trade name "Avalution Nano Tape." The tape is advertised as being usable on a variety of surfaces, including glass, metal, kitchen cabinets, and tile.

[0074] Samples 3 and 4 were fabric adhesive tapes / laminates commercially available for securing fabric to skin. Sample 3 is available from 3M under the trade name "Essentials Wardrobe Tape Strips." Sample 4 is available as Hollywood Fashigh Secrets® Fashion Tape.

[0075] Sample 5 was an adhesive commercially available as a general purpose adhesive. Sample 5 is available under the trade name "Ivy Grip Tape, Washable Adhesive Tape." This tape is listed as being capable of attaching products to walls, cell phone holders, etc.

[0076] Sample 6 is commercially available and sold under the trade name “The Stikk brand gel pad.” These gel pads are utilized to attach electrical cord / wire bundles to a wall or respective enclosure.

[0077] Samples 7 to 9 are commercially available PFA.

[0078] It should be noted that Samples 1-4 are currently available on the market. None are currently utilized as PFA. Also, as opposed to the stated uses of Samples 1 and 2, for example, the PFA is temporary. In other words, the PFA is typically removed a few hours after application. In contrast, the stated uses of Samples 1 and 2 indicate that these tapes are intended to provide much longer term (e.g., months to years) adhesion between products.

[0079] The application of the use of Samples 3 and 4 is more temporary than that of Samples 1 and 2, since their application is to adhere the fabric to the skin. However, these tapes are primarily used for blouse gaps, to secure the neckline, and generally to reduce the likelihood of garment failure. However, the stresses and strains experienced by the adhesive placed at the neckline are very different from those experienced by the PFA. The area where the PFA is placed during use can undergo a much greater range of motion than the neckline, so the stresses and strains experienced by the PFA are much greater.

[0080] Table 1 shows the total surface energy, polar component of the surface energy, surface polarity, yield stress and relaxation time of the adhesives that were measured.

[0081] [Table 1]

[0082] Additionally, peel force testing and adhesive residue testing were performed on a number of these samples, with the data provided below in Table 2. The peel force testing data was obtained according to the peel force testing described herein, and the residue testing was performed according to the adhesive residue testing described herein.

[0083] [Table 2]

[0084] To provide good initial attachment, stay in place, and removal characteristics, the PFA of the present disclosure may exhibit a peel force of at least 1.0 N, more preferably about 1.1 N, or most preferably about 1.2 N, according to the peel force test, but may specifically include all values ​​within this range and any range created thereby. Also, to reduce the possibility of leaving residue and / or leaving the backsheet of the absorbent article, it is contemplated that the peel force may be less than about 5 N, more preferably less than about 4 N, or most preferably about 3 N or less, but may specifically include all values ​​within this range and any range created thereby. Thus, the PFA of the present disclosure may exhibit a peel force of at least 1.0 N to about 5.0 N, more preferably about 1.0 N to about 4.0 N, or most preferably about 1.0 N to about 3.0 N, but may specifically include all values ​​within this range and any range created thereby.

[0085] Sample 4' is an acrylate based adhesive version of Sample 4. Sample 4' is sold under the same trade name as Sample 4. It is also noteworthy that according to the Adhesive Residue Test Method, Samples 1-4 and Sample 4' do not leave any residue on the undergarment upon removal of the article.

[0086] For the peel and residue test data in Table 2, pads were constructed from the following materials: (i) an 18 gsm spunbond bico nonwoven topsheet, (ii) a 55 gsm spunlace secondary topsheet, (iii) a pair of pulp airlaid cores, each of 135 gsm, (iv) a pair of superabsorbent polymer layers substantially free of airfelt, and (v) a 12 gsm film backsheet.

[0087] For samples utilizing "full coverage" adhesive, the adhesive was applied to cover an area of ​​the pad of 300mm x 59mm. For sample 7, the adhesive basis weight was 15gsm. The adhesive residues were applied to the garment-facing surfaces of the articles at the basis weight they were purchased at.

[0088] Figures 1A, 1B, 2A, and 2B show that Samples 1-4 are within the scope of the claims for adhesives that perform well on both cotton and microfiber underwear. Figures 1A, 1B, 2A, and 2B are graphs showing the storage modulus-1 and tan δ-1 values ​​of Samples 1-9, respectively, in the frequency range of 0.01 Hz to 1 Hz. As will be appreciated, this frequency range can indicate the initial bonding and remaining in place function of the PFA and the absorbent article. Specifically, Figures 1A and 1B show graphs of the storage modulus-1 values ​​of Samples 1-4 and 5-9, respectively.

[0089] 2A and 2B show graphs of tan δ-1 for Samples 1-4 and 5-9, respectively. As the graphs show, Samples 1-4 are within the range of the PFAs of the present disclosure and provide good adhesion to both cotton and microfiber underwear. In contrast, Samples 5-9 do not provide good adhesion to microfiber underwear.

[0090] Figures 3A, 3B, 4A, and 4B are graphs showing the storage modulus-2 and tan δ-2 values ​​of Samples 1-9, respectively, in the frequency range of 50 Hz to 100 Hz. As is known, this frequency range can indicate the cohesiveness of the adhesive and can be an indication of how the adhesive will perform during removal from the underwear. Specifically, Figures 3A and 3B show graphs of the storage modulus-2 values ​​of Samples 1-4 and Samples 5-9, respectively.

[0091] 4A and 4B show graphs of the tan δ-2 values ​​of Samples 1 to 4 and Samples 5 to 9, respectively. As shown, Samples 1 to 4 are within the range of tan δ-2 previously described.

[0092] Figures 5A to 5E and Figures 6A to 6E are graphs showing the behavior of the tan δ-1 value at 25° C. and the behavior of the tan δ-1 value at 37° C. for Samples 1 to 4 and Samples 5 to 9, respectively. Figures 7A to 7E and Figures 8A to 8E are graphs showing the behavior of the storage modulus-1 value at 25° C. and the behavior of the storage modulus-1 value at 37° C. for Samples 1 to 4 and Samples 5 to 9, respectively.

[0093] The behavior of the PFA of the present disclosure at both of these temperature points may be significant. Without wishing to be bound by theory, it is believed that during use, the user's underwear is close to body temperature (37°C) or at least a few degrees / few degrees below body temperature. However, during application of the absorbent article, the underwear is pulled down and the absorbent article is applied. While the underwear is lowered down, it is believed that the underwear is close to or at least approaches room temperature (25°C) and at this temperature the initial application is made. Following application of the article to the underwear, the underwear (along with the absorbent article) is pulled up into the wear position. In this position, it is believed that both the absorbent article and the underwear will warm up. It is also believed that within a short period of time, both the absorbent article and the underwear will be close to body temperature or at least asymptotically approach body temperature. With this in mind, it is further believed that an adhesive having a similar tan δ-1 range of 0.28 to 1.2 at room temperature (25°C) and body temperature (37°C), and having a storage modulus-1 value of less than 85 KPa in the frequency range of 0.01 Hz to 0.1 Hz, will form a better attachment to undergarments, whether the undergarment is made from cotton or microfiber material.

[0094] 9A and 9B show graphs of bond compliance values ​​and peel compliance values, respectively.

[0095] 10A and 10B show micro-CT images of Samples 1 and 6, respectively, showing their attachment to a microfiber undergarment substrate. As shown, in FIG. 10A, there is no visible gap between the adhesive 1000 and the microfiber undergarment substrate 1010. In contrast, in FIG. 10B, there is a substantial gap between the adhesive 1050 and the microfiber undergarment substrate 1060. The gap also exists for the entire length within the analyzed micro-CT image.

[0096] 11A-11D show SEM images of Sample 7 and an attempt to bond it to a portion of a microfiber undergarment. A cross section of the adhesive 1150 and the microfiber undergarment 1160 was taken to show how the adhesive 1150 bonds to only some of the fibers in the undergarment 1160. Specifically, in FIGS. 11C and 11D, the adhesive 1150 contacts portions of fiber bundles at high points within the undergarment 1160. For clarity, the undergarment comprises fiber bundles that are woven with other fiber bundles. Thus, each fiber bundle has high points where it crosses over the fiber bundles that run in a direction perpendicular to itself, and low points where it crosses under the next adjacent fiber that runs perpendicular to itself. The adhesive 1150 is shown with some adhesion to the high points of the fiber bundles.

[0097] 12A-12D show SEM images of sample 4 and how it bonds to a portion of a microfiber underwear 1250. In contrast to adhesive 1150 (shown in FIGS. 11A-11D), adhesive 1200 is shown to not only adhere to the high points of the fibers, but also to a larger surface area to the various fiber bundles. In the images provided by FIGS. 12A-12D, adhesive 1200 flows to such an extent that in cross section under SEM, in contrast to the images of FIGS. 11A-11D, there are no gaps between adhesive 1200 and the fibers oriented perpendicular to the plane of the image. Thus, adhesive 1200 is disposed on these fibers such that a portion of their periphery in the plane of the image is coated with adhesive. Also, adhesive 1200 can bond to the periphery of the fibers such that adhesive flows between adjacent fibers perpendicular to the plane of the image, as shown.

[0098] Absorbent articles The PFA of the present disclosure may be utilized in numerous absorbent articles to attach the article to the outer shell of a user's undergarment or material, as in the case of disposable inserts. Exemplary articles in which the PFA of the present disclosure may be utilized include menstrual pads, sanitary pads, incontinence pads, male incontinence guards, liners, absorbent inserts for durable panties, absorbent inserts for disposable diapers, etc. The PFA of the present disclosure may be, among others, a removable and repositionable adhesive similar to one of the samples available from 3M Company (St. Paul, Minn.).

[0099] Generally, absorbent article manufacturers do not compound / blend PFA adhesives in-house, but instead purchase PFA from an adhesive supplier. In such cases, the adhesive supplier may make PFA within the scope of the present disclosure and then apply the PFA to a material web, such as a film. The adhesive manufacturer may then provide the film with the PFA applied thereto to the absorbent article manufacturer. After obtaining the film with the PFA applied thereto, the absorbent article manufacturer may manufacture at least one of feminine hygiene articles, adult incontinence pads, male incontinence guards, or absorbent liners or absorbent inserts for durable panties and / or disposable diapers, or combinations thereof. The absorbent article manufacturer may then apply the PFA to the backsheet of the absorbent article being produced.

[0100] Similarly, an absorbent article manufacturer producing at least one of feminine hygiene articles, adult incontinence pads, male incontinence guards, or absorbent liners or inserts for durable panties and / or disposable diapers, or combinations thereof, can obtain the PFA of the present disclosure from an adhesive supplier, and the absorbent article manufacturer can then apply the PFA to a portion of the backsheet and / or garment-facing surface of the absorbent article.

[0101] The absorbent article of the present disclosure includes a topsheet, a backsheet, and an absorbent system disposed between the topsheet and the backsheet. The topsheet and the backsheet are joined, directly or indirectly, at the periphery, generally to the exterior of the absorbent system. The PFA of the present disclosure is applied at least partially to the garment-facing side of the absorbent article, including at least a portion of the backsheet.

[0102] Any suitable pattern of PFA of the present disclosure may be utilized. In one example, a plurality of stripes oriented generally parallel to the longitudinal axis of the article may be utilized, for example, 2-35 stripes. In another example, a plurality of stripes oriented generally parallel to the transverse axis of the article may be utilized, for example, 2-70 stripes. A combination of longitudinally oriented stripes and / or transversely oriented stripes may be utilized. Any suitable spacing between adjacent stripes may be utilized, and any suitable stripe width may be utilized. Variable spacing between adjacent stripes and / or variable stripe widths are also contemplated. Examples of application of PFA to absorbent articles are also disclosed in U.S. Patent Application No. 16 / 809601, entitled "Absorbent Article with Adhesive Pattern," filed March 5, 2020, and U.S. Patent Application Publication No. 2016 / 0166447.

[0103] Exemplary arrangements of PFA on the garment-facing surface of an absorbent article are shown in Figures 13 and 14. Figure 13 depicts an exemplary absorbent article (10) according to the present disclosure as viewed from the garment-facing side. The articles in both Figures 13 and 14 have a longitudinal axis (I), a transverse axis (II), a front end portion (i), a rear end portion (ii), and a central portion (iii), and are either wingless sanitary napkins (10) (Figure 13) or winged sanitary napkins (10) (Figure 14) whose backsheet (20) includes a pattern of PFA (30) in the form of a series of stripes of PFA (40) and stripes without PFA (50).

[0104] Optional wings (also called "side panels") are a common element in absorbent articles according to the present invention that are well known to those skilled in the art. The intent of the wings is to protect the sides of the undergarment, and typically the wings are folded along the crotch area of ​​the undergarment and attached under the undergarment. The wings may be provided as separate members and attached to the article, typically a panty liner or sanitary napkin, or they can be integral with the material of the absorbent article, for example by being integrated with an extension of the topsheet, backsheet, or both.

[0105] As mentioned above, for the purposes of the present invention, the wings are not considered part of the backsheet (even if they are formed by integrating with the extensions). The wings typically include PFA on the backsheet side to secure them under the crotch of the undergarment, and any typical PFA distribution can be used in the present invention, such as continuous or patterned application, for example, patterned application of PFA on the wings may provide the same benefits as patterned PFA application on the backsheet of the article when the article is removed, reducing the risk of tearing the wing material. For example, at least a portion of the wingback surface may include a patterned application of PFA in the same form as described above for patterned PFA application on the backsheet, for example, with a non-continuous application of PFA, such that any point of said application is never more than 10 mm away from another portion where PFA is not applied. The pattern of PFA may be formed by a plurality of separate or only partially connected elements that may be selected from any possible application pattern, such as stripes, circles, dots, geometric figures, stars, decorative figures, irregular shapes, etc. For example, stripes or squares of PFA are particularly suitable patterns.

[0106] 14 depicts an exemplary absorbent article according to the present invention as viewed from the garment-facing side. The article also includes a PFA pattern on its wings (70) in the form of four squares.

[0107] The topsheet may comprise any suitable substrate. Some examples include films, nonwovens, laminates of films and nonwovens, film-to-film laminates, nonwoven-to-nonwoven laminates, film-to-nonwoven composites, film-to-film composites, and nonwoven-to-nonwoven composites. A laminate of two different materials is considered a combination of the materials after each is made. For example, a film web may be combined with a nonwoven web via mechanical processing, adhesives, ultrasonic or fusion bonding, etc.

[0108] A composite of two different materials is considered a combination of materials when one of the materials is made. For example, a semi-molten film web can be extruded onto a nonwoven fabric. This composite does not require additional bonding because the semi-molten material can flow to some extent into the gaps between the nonwoven fibers.

[0109] Regardless of the form of the topsheet, it is preferred that the topsheet is compliant, soft-feeling, and non-irritating to the wearer's skin and hair. Additionally, the topsheet is liquid pervious, allowing liquids (e.g., menses and / or urine) to readily penetrate through its thickness. Suitable topsheets may be manufactured from a wide range of materials, including woven and nonwoven materials (nonwoven webs of fibers); polymeric materials, such as perforated molded thermoplastic films, perforated plastic films, and hydroformed thermoplastic films; porous foams; reticulated foams, reticulated thermoplastic films; and thermoplastic scrims. Suitable woven and nonwoven materials may be composed of natural fibers (e.g., wood or cotton fibers), synthetic fibers (e.g., polymeric fibers, such as polyester, polypropylene, or polyethylene fibers), or combinations of natural and synthetic fibers. When the topsheet comprises a nonwoven web, the web may be manufactured by a number of well-known techniques. For example, the web may be spunbonded, carded, wet-laid, meltblown, hydroentangled, combinations of the above, and the like.

[0110] The topsheet of the present disclosure may be provided with a texture, such as protrusions or depressions. The protrusions and / or depressions may be treated to be hydrophobic or hydrophilic as desired. Some suitable examples of protrusions and depressions, and their respective treatments and methods, are described in U.S. Patent Application Publication Nos. 2017 / 0258955, 2018 / 0071151, 2017 / 0027774, 2017 / 0029994, 2018 / 0216269, 2019 / 0374405, 2019 / 0380887, and 2019 / 0298587.

[0111] As mentioned above, the absorbent article of the present disclosure includes an absorbent system disposed between the topsheet and the backsheet. The absorbent system may include several layers. For example, a layer of material closest to the topsheet (often called an acquisition layer or secondary topsheet) may be utilized to rapidly acquire the insult of liquid from the topsheet.

[0112] The secondary topsheet or acquisition layer may comprise any suitable material. Some examples include films and nonwovens, or laminates or composites thereof. Film-based secondary topsheets can provide a good barrier against rewetting if used correctly. However, care must be taken to ensure that film secondary topsheets contain suitable fluid transport openings to allow the insult of liquid acquired from the topsheet to pass through to one or more storage layers.

[0113] A nonwoven-based secondary topsheet may also be utilized. For example, the secondary topsheet of the present disclosure may comprise a thin woven layer or a nonwoven, the latter including carded resin-bonded nonwoven, embossed carded resin-bonded nonwoven, bulky carded resin-bonded nonwoven, carded air-through bonded nonwoven, carded thermal bonded nonwoven, spunbonded nonwoven, etc. A variety of fibers may be used in the secondary topsheet or acquisition layer, including natural fibers such as wood pulp, cotton, wool, and biodegradable fibers such as polylactic acid fibers, and synthetic fibers such as polyolefins (e.g., polyethylene and polypropylene), polyesters, polyamides, synthetic cellulose derivatives (e.g., RAYON®, Lyocell), cellulose acetate, bicomponent fibers, and blends thereof. The basis weight of the secondary topsheet or acquisition layer may vary depending on the desired application. Some suitable secondary topsheets are described in U.S. Patent Application Publication Nos. 2020 / 0306099, entitled "FLUID MANAGEMENT LAYER FOR AN ABSORBENT ARTICLE," 2020 / 0315870, entitled "Fluid Management Layer For An Absorbent Article," and 2020 / 0315861, entitled "Absorbent Layer For An Absorbent Article." Additional exemplary secondary topsheets are described in U.S. Patent Application Publication Nos. 10,532,123, 2019 / 0247244, and 2018 / 0098893.

[0114] The absorbent system may additionally or independently include an absorbent core. The absorbent core may be formed from any material known to those skilled in the art. Examples of such materials include multiple plies of creped cellulose wadding, fluffed cellulose fibers, wood pulp fibers also known as airfelt, woven fibers, fiber blends, fiber clumps or cores, aeolian webs of fibers, webs of polymeric fibers, and blends of polymeric fibers. Other suitable absorbent core materials include absorbent foams such as polyurethane foams or high internal phase emulsion ("HIPE") foams. Suitable HIPE foams are disclosed in U.S. Patent Nos. 5,550,167, 5,387,207, 5,352,711, and 5,331,015. The absorbent core may include superabsorbent materials such as absorbent gelling materials (AGM) containing AGM fibers, as known in the art. Thus, the absorbent core may constitute a layer that includes a superabsorbent material.

[0115] The absorbent core may include blends of components and / or a multiplicity of layers. For example, one layer may include a mixture of cellulose (pulp) and AGM. Another layer may include a foam layer, such as a HIPE foam layer or a polyurethane foam layer. Additional HIPE foam layer configurations are possible. For example, the HIPE foam or a portion thereof may be deposited on a nonwoven web. Such structures are described in further detail in U.S. Patent Application Publication Nos. 2015 / 0313770, 2015 / 0335498, 2015 / 0349391, 2017 / 0071795, 2017 / 0119587, and 2017 / 0119597. Additional structures are disclosed in U.S. Patent Application Publication Nos. 10,045,890, 9,956,586, and 10,016,779. As yet another example, the absorbent core layer may comprise a nonwoven web to which the AGM is deposited and secured by an adhesive. Such processes and structures are described in further detail in U.S. Patent Nos. 8,187,240, 7,838,722, 8,735,645, 8,784,594, and 9,492,334.

[0116] Numerous combinations of the above layers are possible. For example, a nonwoven / AGM layer can be bonded to a cellulose layer and / or a HIPE foam layer. As another example, a cellulose layer can be bonded to a HIPE foam layer and / or a polyurethane foam layer. As yet another example, a layer containing a mixture of cellulose and AGM can be bonded to a HIPE foam layer and / or a polyurethane foam layer. Any of the above combinations may be utilized in combination with each other and / or may be duplicated, for example, when a larger absorbent core may be required in the context of adult incontinence. For example, a nonwoven / AGM layer can be bonded to a cellulose layer, which in turn can be bonded to another cellulose layer, which in turn can be bonded to a nonwoven / AGM layer.

[0117] Additional examples of absorbent cores include those with multiple layers. In one example, the absorbent core may include a distribution layer substantially free of AGM, a superabsorbent layer substantially free of pulp, a second distribution layer substantially free of AGM, and a second superabsorbent layer substantially free of pulp. These layers may be arranged in any suitable manner. For example, the first distribution layer may be disposed adjacent to the secondary topsheet with the first superabsorbent layer disposed between the first distribution layer and the second distribution layer. The second superabsorbent layer may be disposed between the second distribution layer and the backsheet. Alternatively, the second superabsorbent layer may be disposed between the first superabsorbent layer and the second distribution layer. Or in another example, the first distribution layer may be disposed between the first superabsorbent layer and the second superabsorbent layer. Examples of such absorbent core structures are provided in further detail in U.S. Patent Application Publication Nos. 2020 / 0375810(A1), 2019 / 0314212(A1), 2018 / 0098893(A1), and 2018 / 0098896(A1).

[0118] In some absorbent articles, the absorbent core may be relatively thin, having a thickness of less than about 5 mm, or less than about 3 mm, or less than about 1 mm. The thickness may be determined by any means known in the art, such as by measuring the thickness at a midpoint along the longitudinal centerline of the pad while under a uniform pressure of 1.72 kPa. The overall thickness of the absorbent article may be relatively thin as well. In some cases, panty liners may range from 1.5 mm to about 3.0 mm. Menstrual pads may have a thickness ranging from 2.0 mm to about 3.5 mm. Adult incontinence pads may have a thickness of about 2.6 mm to about 6.5 mm.

[0119] With regard to AGM, polyacrylate-based materials, typically partially neutralized polymers, are commonly incorporated into absorbent articles and known as superabsorbent polymers or superabsorbents, and are crosslinked. Polyacrylate materials are typically neutralized with sodium, with carboxylate groups pendant from the main polymer chain. On contact with water, the sodium separates and goes into solution, leaving only the carboxyl ions behind. Being negatively charged, these ions repel each other, which causes the polymer to dissolve and absorb more water, which is instead attracted by the carboxyl ions, making more available carboxyl ions. Hydrogen in the water is captured by the polyacrylate through atomic bonds related to the polar forces between the atoms. The crosslinks linking the different polymer chains result in a three-dimensional structure, constituting a swollen gel upon liquid absorption.

[0120] Absorbent gelling materials that may be included in the absorbent core may be selected from among the polyacrylate-based polymers described in European Patent No. 05023061.4, filed on October 21, 2005 in the name of Procter and Gamble Company. As explained in the referenced applications, polyacrylate-based materials that are very slightly crosslinked or substantially not crosslinked at all are incorporated into absorbent articles for absorbing proteinaceous or serous body fluids, such as menses, blood, plasma, vaginal secretions, and mucus or milk, but provide improved absorption and retention capacity of such body fluids, as well as improved absorption rates, particularly for menses or blood, as compared to conventional crosslinked superabsorbents.

[0121] The absorbent gelling material may typically be used in the form of discrete particles. Such absorbent gelling materials may be of any desired shape, such as spherical or semispherical, cubic, rod-like polyhedrons, etc. Shapes having a maximum dimension / minimum dimension ratio such as needles and flakes are also contemplated for use herein. Agglomerates of absorbent gelling material particles may also be used.

[0122] The absorbent core may include a core wrap, ie, a thin layer of fluid permeable material (usually tissue paper or a thin nonwoven layer) that encases the core to maintain its integrity during manufacture and use of the article.

[0123] The absorbent article may include additional components such as side cuffs, typically found in incontinence pads, or side wings or flaps, typically found in sanitary napkins. If the absorbent article includes side flaps or wings, these side flaps or wings may comprise the PFA of the present disclosure.

[0124] The absorbent articles herein are preferably disposable after a single use and are usually commercially available in packages containing multiple units, and in some cases may be individually wrapped.

[0125] The backsheet of the absorbent article of the present disclosure is the outer layer of the article on the side facing the garment. The PFA is applied to the garment-facing surface of the backsheet. If the outer layer on the garment-facing side of the absorbent article is a composite material (such as a laminate of film and nonwoven material) for the purposes of this disclosure, the term "backsheet" refers only to the outermost layer of the layers forming the composite material. For example, for the purposes of this disclosure, if a NW / PE film laminate is applied with the PE film being the outer layer on the garment-facing surface to which the fastening adhesive is applied, the term "backsheet" refers only to the outer PE film layer.

[0126] The backsheet of the absorbent article of the present invention is a plastic film, preferably flexible and soft. As used herein, the term "flexible and soft" refers to a material that is malleable, easily conforms to the general shape and contours of the human body, and can provide the user with a pleasant tactile sensation on the skin. The backsheet prevents articles that contact the absorbent article, such as bed sheets, pants, pajamas, and underwear, from getting wet by the exudates absorbed and retained in the absorbent core. The backsheet can also be liquid-impermeable yet vapor-permeable ("breathable"). In this case, typically a microporous plastic film is used that is permeable to water vapor while remaining essentially impermeable to liquids.

[0127] The backsheet may be a plastic film having a basis weight of less than 40 gsm, or less than 30 gsm, or less than 24 gsm, or less than 18 gsm, or less than 15 gsm, or less than 13 gsm. Any kind of plastic film may be used as the backsheet according to the present invention. Suitable films may be formed by thermoplastic polymer materials and may be obtained by known film manufacturing processes. The plastic film may be selected from monolayer or multilayer films, which may be obtained, for example, by monolayer extrusion or multilayer coextrusion processes. For example, US Patent Application Publication No. 2014 / 0248484 discloses a method for producing a thin plastic film usable as the backsheet of the present invention, which is an initial film web made of a thermoplastic polymer material containing a polyethylene matrix, in which 1 to 70 parts by weight of polypropylene per 100 parts by weight of the polyethylene matrix is ​​guided through a roll nip that is heated and then cooled, whereby the initial film web is heated only until the polyethylene matrix material is melted but below the melting temperature of the polypropylene.

[0128] The plastic film usable herein as a backsheet may comprise a single polymer or a blend of different polymers. In addition to the polymer, the plastic film of the present disclosure may comprise chemical additives such as, for example, pigments, dyes, light protectants, antioxidants, and inert materials such as titanium dioxide, calcium carbonate, or also kaolin, diatomaceous earth, or mixtures thereof. The presence of an inert component, typically calcium carbonate, can enhance the physical properties of the polymer film, especially its heat resistance, which may be beneficial in the context of the present invention, where the backsheet film is typically heat sealed along its periphery to the topsheet of the absorbent article. Inert materials may also be included in the plastic film, which is mechanically stretched when cooled so that the inert particles form a network of channels, which allows the passage of water vapor while maintaining good permeability. Such films are usually identified as "microporous films" and are suitable as backsheets of the present invention, where they may provide improved breathability in absorbent articles (as is well known in the art).

[0129] The plastic film usable herein as the backsheet of the present invention is preferably a thermoplastic polyolefin-based film.The plastic film of the present invention can be, for example, a polyethylene (PE)-based film, a polypropylene (PP)-based film, or a PE / PP blend-based film.

[0130] When a film is referred to as being "based" on a polymer (e.g. PE) or a mixture of polymers (e.g. PE / PP blend), it is intended that the majority of the film is composed of the polymer(s), preferably based on more than 80% by weight, even more preferably more than 90% by weight. The remaining mass of the film may be formed by other polymers and conventional film additives well known in the art.

[0131] As mentioned above, the backsheet forms the garment-facing surface of the absorbent article on which the fastening adhesive is placed. Prior to use of the absorbent article, the PFA-coated areas are typically protected from contamination and unwanted adhesion to other surfaces by a protective cover means, such as a silicone-coated release paper, a silicone-coated plastic film, or any other easily removable cover. The protective cover means may be provided as a single piece or multiple pieces, for example, to cover the individual adhesive areas (e.g., on the backsheet and on the wings). The protective cover means may also perform other functions, such as providing individual packaging of the article or providing a disposal function as is well known in the art. Any commercially available release paper or film may be used. Suitable examples include BL 30 MG-A SILOX EI / O, BL 30 MG-A SILOX 4 P / O available from Akrosil Corporation, and M&W film available from Gronau, Germany, code X-5432.

[0132] The PFA of the present disclosure is disposed on the garment-facing surface of the absorbent article, which may include a portion of the backsheet and / or a portion of the wings / side flaps. The PFA on the garment-facing surface can provide good adhesion and removal properties to cotton and microfiber undergarments, as described. The PFAs can be evaluated for the properties of the present disclosure before applying them on the backsheet of each absorbent article.

[0133] Table 3 is provided for the convenience of the reader. Table 3 contains a non-exhaustive list of characteristics, as well as a non-exhaustive list of corresponding values, for each of the characteristics discussed herein for the PFAs of the present disclosure. The PFAs of the present disclosure need not exhibit all of these characteristics.

[0134] [Table 3]

[0135] Additional embodiments: Example A. A method of using an adhesive for absorbent articles, the method comprising the steps of formulating an adhesive, the adhesive having the following: a tan δ-1 value of 0.28 to 1.2, more preferably 0.28 to 1.13, or most preferably 0.28 to 0.51, over a frequency range of 0.01 Hz to 1 Hz at 37° C., according to the Frequency Sweep-Oscillation Rheometry Test Method; a storage modulus-1 value of less than 85 kPa, more preferably 74 kPa or less, or most preferably 57 kPa or less, over a frequency range of 0.01 Hz to 1 Hz, according to the Frequency Sweep-Oscillation Rheometry Test Method; a tan δ-2 value of 1.9 or less, more preferably 1.8 or less, or most preferably 1.38 or less, over a frequency range of 50-100 Hz at 37°C according to a Dynamic Rheometry test method; a storage modulus-2 value of greater than 40 kPa, more preferably 73 kPa or more, or most preferably 146 kPa or more, over a frequency range of 50-100 Hz at 37°C according to a Frequency Sweep-Oscillatory Rheometry test method, wherein the storage modulus-2 value is greater than the storage modulus-1 value; and providing the adhesive to a manufacturer of absorbent articles. Example A1. A method of making an absorbent article comprising the steps of obtaining a topsheet material, obtaining an absorbent material, obtaining a backsheet material, and obtaining an adhesive, the adhesive having the following: a tan δ-1 value of 0.28 to 1.2, more preferably 0.28 to 1.13, or most preferably 0.28 to 0.51, over a frequency range of 0.01 Hz to 1 Hz at 37°C, according to a Frequency Sweep-Oscillation Rheometry Test Method; a storage modulus-1 value of less than 85 kPa, more preferably 74 kPa or less, or most preferably 57 kPa or less, over a frequency range of 0.01 to 1 Hz at 37°C, according to a Frequency Sweep-Oscillation Rheometry Test Method; and a storage modulus-2 value of greater than 40 kPa, more preferably greater than 73 kPa, or most preferably greater than 146 kPa, over a frequency range of 50-100 Hz at 37° C. according to a Frequency Sweep-Oscillation Rheometry test method, wherein the storage modulus-2 value is greater than the storage modulus-1 value; assembling the topsheet material, absorbent material, and backsheet material; and applying an adhesive to a garment-facing surface of the backsheet. Example A2. A method of making an absorbent article comprising the steps of obtaining a topsheet material, obtaining an absorbent material, and obtaining a backsheet material, the backsheet material comprising an adhesive disposed on a garment-facing surface of the backsheet, the adhesive having the following properties: a tan δ-1 value of 0.28 to 1.2, more preferably 0.28 to 1.13, or most preferably 0.28 to 0.51, over a frequency range of 0.01 Hz to 1 Hz at 37°C, according to a Frequency Sweep - Oscillatory Rheometry Test Method; a tan δ-1 value of less than 85 kPa, more preferably less than 74 kPa, or most preferably less than 74 kPa, over a frequency range of 0.01 Hz to 1 Hz at 37°C, according to a Frequency Sweep - Oscillatory Rheometry Test Method. a storage modulus-1 value of preferably 57 kPa or less; a tan δ-2 value of 1.9 or less, more preferably 1.8 or less, or most preferably 1.38 or less, over a frequency range of 50-100 Hz at 37°C, according to a Frequency Sweep-Oscillation Rheometry test method; a storage modulus-2 value of greater than 40 kPa, more preferably 73 kPa or more, or most preferably 146 kPa or more, over a frequency range of 50-100 Hz at 37°C, according to a Frequency Sweep-Oscillation Rheometry test method, wherein the storage modulus-2 value is greater than the storage modulus-1 value; and assembling the topsheet material, the absorbent material, and the backsheet material. Example A3. The method of Examples A-A2, wherein the adhesive exhibits a total surface energy of less than 25 millijoules per square meter and less than 10% polar content when measured according to the Total Surface Energy Method disclosed herein. Example A4. The method of any of Examples A-A3, wherein the adhesive is polyacrylate-based. Example A5. The method of any of Examples A-A3, wherein the adhesive comprises a mixture of ethylene vinyl acetate and a styrene block copolymer. Example A6. The method of any of Examples A-A5, wherein the adhesive exhibits a tan δ-2 of 0.25 to 1.9, or more preferably 0.25 to 1.8, or most preferably 0.25 to 1.38 in the frequency range of 50 Hz to 100 Hz at 37°C. Example A7. The adhesive has a viscosity of about 10 mJ / m 2~about 25mJ / m 2 , more preferably about 12.5 mJ / m 2 ~about 25mJ / m 2 , or most preferably about 15 mJ / m 2 ~about 25mJ / m 2 The method according to any one of Examples A to A6, which shows a surface energy of Example A8. The method of example A7, wherein the adhesive exhibits a polar component of the surface energy between 1% and 10%, more preferably between 2% and 10%, or most preferably between 3% and 10%. Example A9. The method of any of Examples A-A8, wherein the adhesive has a storage modulus-1 value of 1 kPa to 84 kPa, more preferably 3 kPa to 74 kPa, or most preferably 12 kPa to 57 kPa at 37°C and a frequency between 0.01 to 1 Hz. Example A10. The method of any of Examples A-A9, wherein the adhesive has a storage modulus-1 value at 37° C. and 1 Hz of from 5 kPa to 84 kPa, more preferably from 5 kPa to 80 kPa, or most preferably from 5 kPa to 74 kPa. Example A11. The method of any of Examples A-A10, wherein the adhesive has a storage modulus-1 value at 37°C and 0.01 Hz of from 1 kPa to 50 kPa, more preferably from 1 kPa to 40 kPa, or most preferably from 1 kPa to 30 kPa. Example A12. The method of any of Examples A-A11, wherein the adhesive exhibits a tan δ-1 value of 0.28 to 0.9 at 37° C. and a frequency of 0.01 Hz. Example A13. The method of any of Examples A-A12, wherein the adhesive exhibits a tan δ-2 value of 0.25-1.9, more preferably 0.25-1.8, or most preferably 0.25-1.38 at 37°C and a frequency of 50-100 Hz. Example A14. The method of any of Examples A-A13, wherein the adhesive exhibits a tan δ-1 value of 0.28 to 1.2, more preferably 0.28 to 1.13, or most preferably 0.28 to 0.51 in the frequency range of 0.01 to 0.1 Hz at both 25°C and 37°C. Example A15. The method of any of Examples A-A14, wherein the adhesive exhibits a relaxation time at a temperature of 37° C. of 100 seconds or less, more preferably 30 seconds or less, or most preferably 20 seconds or less. Example A16. The method of any of Examples A-A15, wherein the adhesive exhibits a yield stress of 32 kPa or more, more preferably 40 kPa or more, or most preferably 50 kPa or more. Example A17. The method of example A16, wherein the adhesive exhibits a yield stress of from about 32 kPa to about 100 kPa, more preferably from about 40 kPa to about 100 kPa, and most preferably from about 50 kPa to about 100 kPa. Example B: A panty fastening adhesive for placement on a garment-facing surface of a disposable absorbent article, the adhesive having: a tan δ-1 value of 0.28 to 1.2, more preferably 0.28 to 1.13, or most preferably 0.28 to 0.51, over a frequency range of 0.01 Hz to 1 Hz at 37° C., according to the Frequency Sweep-Oscillatory Rheometry Test Method; a storage pressure of less than 85 kPa, more preferably 74 kPa or less, or most preferably 57 kPa or less, from 0.01 to 1 Hz at 37° C., according to the Frequency Sweep-Oscillatory Rheometry Test Method. a tan δ-2 value of 1.9 or less, more preferably 1.8 or less, or most preferably 1.38 or less, over a frequency range of 50-100 Hz at 37° C., according to a Frequency Sweep-Oscillation Rheometry test method; and a storage modulus-2 value of greater than 40 kPa, more preferably greater than 73 kPa, or most preferably greater than 146 kPa, over a frequency range of 50-100 Hz at 37° C., according to a Frequency Sweep-Oscillation Rheometry test method, wherein the storage modulus-2 value is greater than the storage modulus-1 value. Example B1: The adhesive described in Example B, wherein the adhesive exhibits a total surface energy of less than 25 millijoules per square meter and less than 10% polar content when measured according to the Total Surface Energy Method disclosed herein. Example B2: The adhesive according to any of the examples B to B1, wherein the adhesive comprises a mixture of ethylene vinyl acetate and styrene block copolymers or is polyacrylate-based. Example B3: The adhesive according to any of Examples B to B2, wherein the adhesive exhibits a tan δ-2 value of 0.25 to 1.9, more preferably 0.25 to 1.8, or most preferably 0.25 to 1.38 in the frequency range of 50 Hz to 100 Hz at 37°C. Example B4: The adhesive has a viscosity of about 10 mJ / m 2 ~about 25mJ / m 2 , more preferably about 12.5 mJ / m 2 ~about 25mJ / m 2 , or most preferably about 15 mJ / m 2 ~about 25mJ / m 2 The adhesive according to any one of Examples B to B3, which exhibits a surface energy of: Example B5: The adhesive according to any of Examples B to B4, wherein the adhesive exhibits a polar component of the surface energy between 1% and 10%, more preferably between 2% and 10%, or most preferably between 3% and 10%. Example B6: The adhesive according to any of Examples B to B5, wherein the adhesive has a storage modulus-1 value of 1 kPa to 84 kPa, more preferably 3 kPa to 74 kPa, or most preferably 12 kPa to 57 kPa at 37°C and a frequency of 0.01 to 1 Hz. Example B7: The adhesive according to any of Examples B to B6, wherein the adhesive has a storage modulus-1 value at 0.01 Hz at 37° C. of 1 kPa to 50 kPa, more preferably 1 kPa to 40 kPa, or most preferably 1 kPa to 30 kPa. Example B8: The adhesive according to any of Examples B to B7, wherein the adhesive exhibits a tan δ-1 value of 0.28 to 0.9 at 37° C. and a frequency of 0.01 Hz. Example B9: The adhesive according to any of Examples B to B8, wherein the adhesive exhibits a tan δ-2 value of 0.25 to 1.9, more preferably 0.25 to 1.8, or most preferably 0.25 to 1.38 at 37° C. and a frequency of 50 to 100 Hz. Example B10: The adhesive according to any of Examples B to B9, wherein the adhesive exhibits a tan δ-1 value of 0.28 to 1.2, more preferably 0.28 to 1.13, or most preferably 0.28 to 0.51 in the frequency range of 0.01 Hz to 0.1 Hz at both 25°C and 37°C. Example B11: The adhesive according to any of Examples B to B10, wherein the adhesive exhibits a relaxation time at a temperature of 37° C. of 100 seconds or less, more preferably 30 seconds or less, or most preferably 20 seconds or less. Example B12: The adhesive according to any of Examples B-B11, wherein the adhesive exhibits a yield stress at 37°C of 32 kPa or greater, more preferably about 40 kPa or greater, or most preferably about 50 kPa or greater, as determined by the Elongation Test Method. Example B13: The adhesive according to any of Examples B to B12, wherein the adhesive exhibits a yield stress of 32 kPa to 100 kPa, more preferably 40 kPa to 100 kPa, or most preferably 50 kPa to 100 kPa. Example B14: A disposable absorbent article comprising a top sheet, a back sheet, and an absorbent core disposed between the top sheet and the back sheet, wherein an adhesive described in any one of Examples B to B13 is disposed on the garment-facing side of the disposable absorbent article.

[0136] Test Method Surface Energy / Contact Angle Method Contact angles on substrates are determined using a goniometer equipped with a gas-tight syringe and a steel needle capable of dispensing a 1.0 μL drop and appropriate image analysis software (a suitable instrument is a DSA100 Drop Shape Analyzer (Kruss GmbH, Hamburg, Germany) or equivalent). Two test fluids are used: Type II reagent water (distilled water) according to ASTM specification D1193-99 and 99+% pure diiodomethane (both available from Sigma Aldrich, St. Louis, MO). The contact angles from these two test fluids can further be used to calculate the surface energy based on Fowkes theory. All tests shall be performed at approximately 23° C.±2° C. and a relative humidity of approximately 50%±2%.

[0137] Contact angle measurements are made on specimens taken from raw materials or from layers of material cut from absorbent articles. When cutting the layers of material from the absorbent article, care is taken not to impart any contamination or deformation to the sample layer in the process. When the test site is on the adhesive, any protective covering that may be present is not removed until the measurement is made, in order to reduce the possibility of contaminating the adhesive layer. The specimen must be of an appropriate size to fit the stage of the goniometer and to accommodate the potential spreading of the applied test fluid. Prepare enough specimens for a total of 20 test sites (10 sites for each test fluid).

[0138] Place the goniometer on a vibration isolation table and level the stage according to the manufacturer's instructions. The video imaging device should have an acquisition rate capable of capturing at least 10-20 images from the time the drop of test fluid hits the surface of the specimen until the image can no longer be resolved from the surface of the specimen. A typical imaging rate is 900 images / second. Depending on the hydrophobicity / hydrophilicity of the specimen, the drop may or may not wet the surface of the specimen rapidly. If the specimen is capable of absorbing the test fluid at a slow rate, images should be captured until no more than 2% of the drop's volume is absorbed by the specimen. If the specimen is capable of absorbing the test fluid rapidly, the first resolved image should be used if the second image shows a volume loss of more than 2%.

[0139] The test specimen is placed on the stage of the goniometer and the hypodermic needle is adjusted to the distance from the surface recommended in the manufacturer's instructions (typically 3 mm). If necessary, the position of the specimen is adjusted to place the test location below the tip of the needle. The video device is focused so that a clear image of the drop on the surface of the specimen can be captured. Image acquisition is started. A 1.0 μL ± 0.05 μL drop of diiodomethane is placed on the specimen. If there is visible deformation of the drop shape due to movement, repeat at a different but equivalent test location. From images where there is less than 2% drop volume loss, take two angle measurements at the drop (one for each drop edge). If the contact angles at the two edges differ by more than 4°, the value shall be excluded and the test repeated at an equivalent location on the specimen. Nine further equivalent locations on the specimen are identified and a total of 10 measurements (20 angle measurements) are repeated. The arithmetic mean of all replicates was calculated and reported as the contact angle with diiodomethane to the nearest 0.01°. Similarly, the contact angle with water as the test fluid was measured and reported as the contact angle with water to the nearest 0.01°.

[0140] To calculate the surface energy, the contact angles for both diiodomethane and water shall be tested as described above. The contact angle values ​​for each test fluid are then used, along with additional information about each test fluid, to calculate, using the Young-Dupre equation and Fowkes theory, the following: Young-Dupré equation (Equation 1) W sl =γ l (cosθ+1) Fowkes theory (Equation 2)

[0141]

number

[0142]

number

[0143] [Table 4] If a purely dispersive solvent such as diiodomethane is used, the polar component is zero, and

[0144]

number

[0145]

number

[0146] Using the surface tension value from the table for diiodomethane and θ (measured value), Equation 4 is transformed into the dispersion component of the surface energy (γ D s ) can be solved, which is 0.01 mJ / m 2 It is reported in units of γ D s Using the values ​​from the table for water and θ (measured value) along with the previously calculated values ​​for P s ) can be solved for the polar components, giving 0.01 mJ / m 2 The total surface energy of the specimen (γ s ) is γ D s+γ P s Calculated as the sum of 0.01 mJ / m 2 where the polar component of the surface energy (γ P s ) into the total surface energy (γ s Calculate the surface polarity by dividing by 100 and then multiplying by 100 and reporting to the nearest 0.01%.

[0147] Frequency Sweep-Oscillatory Rheometry Test Method The oscillatory rheometry test method is used to measure the storage modulus and loss factor (also known as tan δ) of adhesive tapes or hot melt adhesive compositions. The rotational rheometer (DHR 3, TA Instruments, New Castle, DE, USA, or equivalent) allows sample temperature control with an accuracy of 0.5°C or better in the range of at least 0°C to 150°C. The rheometer must have a conventional force control system to allow control of the axial force on the specimen with an accuracy of 0.1 N. The rheometer operates with a 25 mm stainless steel parallel plate tool for hot melt adhesives, or a 20 mm stainless steel parallel plate tool for adhesive tapes, or an 8 mm parallel plate tool configuration if the adhesive tape width is less than 20 mm.

[0148] Preparation of adhesive tape specimens For adhesive tapes, punch out individual specimens for measurement with a circular specimen cutter with a diameter of 20 mm or 8 mm if the adhesive tape width is less than 20 mm. Remove the release film and place the measurement specimen in the center of the lower plate of the rheometer at 23°C ± 0.5°C. Lower the upper rheometer plate until it is in contact with the adhesive tape. Press the upper plate onto the adhesive tape for complete contact using an axial force of about 5-10 N and compress for about 30-90 seconds at 23°C ± 0.5°C. The axial force control is then set to 1.0 N and maintained at a force of ± 0.1 N or less throughout the experiment.

[0149] Preparation of hot melt specimens: The rheometer is heated to 150°C, the adhesive or polymer composition is introduced into the rheometer, the gap is set to 1050 μm, excess overhanging sample is trimmed, and the gap is then set to 1000 μm. (The axial force control of the rheometer is set to 0 N and set to maintain an axial force within ±0.1 N during the experiment, thereby adjusting the gap to compensate for thermal expansion / contraction of the sample itself in addition to the tooling compensation mentioned above, to avoid over- or under-packing.) The rheometer is then allowed to cool to 37°C, or 25°C ±0.5°C if data is to be taken at 25°C.

[0150] measurement: The sample is equilibrated for 300 seconds at 37°C ± 0.5°C (or 25°C ± 0.5°C if data is acquired at 25°C). An oscillatory frequency sweep at 0.1% strain is performed from 0.01 to 100 Hz [1 / s] at 37°C ± 0.5°C (or 25°C ± 0.5°C if data is acquired at 25°C). For logarithmic matters, 10 points per decade are acquired (see frequency table).

[0151] analysis: From the frequency sweep, the storage modulus G' and loss factor (tan δ) are calculated and reported in logarithmic terms from 0.01 to 100 Hz for 10 frequencies per decade. Storage modulus values ​​are in kilopascals (KPa) and are reported to the nearest 0.01 KPa. Loss factor (also known as tan δ) is reported in parts per hundred.

[0152] Yield stress elongation test method The extension test method is used to determine the yield stress of test specimens of the adhesive composition. Thin film test specimens formed from the adhesive composition are analyzed in a rotational rheometer equipped with a special fixture with counter-rotating rollers to measure and record the stress related to the applied tensile strain.

[0153] Equipment Setup The rotational rheometer (ARES G2, TA Instruments, New Castle, DE, USA, or equivalent) is equipped with a fixture with counter-rotating cylindrical metal rollers specifically designed to control the tensile deformation of the film. An example of a suitable fixture is the Extensional Viscosity Fixture, or EVF (EVF, TA Instruments, or equivalent). The rheometer is further equipped with a forced convection oven FCO (FCO, TA Instruments, or equivalent) capable of controlling the temperature from at least -50 to 250°C within a tolerance of 0.5°C, and a cooling system (ACS2, TA Instruments, or equivalent).

[0154] Preparation of test specimens If the adhesive has been applied to a substrate, it is necessary to separate the adhesive before preparing it as a test specimen. This can be done by extracting the adhesive with an organic solvent such as tetrahydrofuran (THF) and then gently evaporating all the solvent at room temperature (20°C to 30°C) to obtain the adhesive for test specimen preparation.

[0155] To prepare the test specimens, 2 g to 10 g of the adhesive composition is placed in a circular polytetrafluoroethane (PTFE) bowl with a flat bottom (diameter 60 mm or 25 mm ± 2 mm) and introduced into a vacuum oven held at 170 ° C. After 15 minutes at ambient pressure, the pressure is reduced to 10 mbar and the adhesive composition is subsequently held at 170 ° C and 10 mbar for 45 minutes to remove air bubbles from the adhesive composition. If 170 ° C is insufficient to melt the adhesive composition, a temperature of 30 ± 10 ° C above the melting temperature of the polymeric material composition is used. The adhesive composition is removed from the vacuum oven and allowed to cool to ambient laboratory conditions (23 ± 2 ° C) over a period of 90 ± 30 minutes, at which point the adhesive composition is removed from the PTFE bowl and placed between two pieces of siliconized paper (e.g., product number 114918, Mondi Group, Hilm, Austria, or equivalent). A metal shim of 500±30 μm thickness is used in the heated press as a spacer to obtain a film thickness of 500 μm when pressed in the heated press at 90° C. for 60 seconds at a pressure sufficient to form a polymer film. If 90° C. is insufficient to press a uniform flat film, a temperature approximately 10±5° C. lower than the melting point of the sample material composition is used so that the sample material composition is in a semi-solid state. The film is stored in a laboratory at 23±2° C. for at least 120 hours prior to testing. Individual specimens for measurement are punched out from the film using a specimen cutter to final specimen dimensions of 20.0 mm x 10.0 mm x 500 μm.

[0156] measurement To secure the specimen film to the EVF, the specimen is pressed briefly against the cylinder of the EVF to secure it to the cylinder surface. The specimen is oriented so that its length is perpendicular to the axis of rotation of the cylinder.

[0157] The specimen mounted on the EVF was then placed in the forced convection oven of the rheometer for thermal conditioning and maintained isothermal at 37±0.5°C for 300±10 seconds. After this time has elapsed, the specimen is mechanically conditioned. To mechanically condition the specimen, the torque transducer is zeroed and the sample is rotated for 0.001 s. -1 for 0.30 seconds and then allowed to relax for 60 seconds (in this method all strains are expressed in terms of Hencky strain, also known as "true strain" or "logarithmic strain").

[0158] The measurements are carried out in an FCO oven at 37°C ± 0.5°C. The strain rate for the measurements is 1s -1 and the strain at maximum elongation is 4.0. After the measurement, the specimen is inspected for rupture. If it has ruptured, the location of the rupture is recorded. If the rupture is approximately centered between the two cylinders of the EVF, the collected data is considered acceptable. Otherwise, if the polymer film rupture is at or near the rotating cylinder, discard the results and perform the measurement again on a duplicate specimen.

[0159] analysis A constant volume is assumed for the calculation of extensional stress. Extensional stress (in kilopascals or kPa) versus Hencky strain data is calculated from the raw torque versus angular displacement data recorded by the rheometer. The data is plotted in a semi-logarithmic format with Hencky strain on the abscissa (linear scale) and extensional stress on the ordinate (logarithmic scale). In this plot, a linear range between 0.7 and 1.3 Hencky strains is determined. The value of the fitted line at zero Hencky strain (i.e., the y-intercept) is defined as the yield stress, which is reported in kilopascals rounded off.

[0160] Peel Force Test Method (for PFA on Microfiber Underwear) This peel force test method is used to determine the force required to peel a strip of microfiber material from a panty fastening adhesive (PFA) on the garment-facing side of an absorbent article. The method is intended to simulate the removal of an absorbent article attached to a user's undergarments during use. Peel force is measured with a constant rate of extension tensile tester (a suitable instrument is MTS Alliance, or equivalent, available from MTS Systems Corp., Eden Prairie, MN, using Testsuite software) interfaced to a computer using a load cell that measures force within 1%-99% of the cell's limits. All tests are performed in a conditioned room at 23°C ± 3°C and 50% ± 2% relative humidity, and test specimens are conditioned in this environment for at least 2 hours prior to testing.

[0161] A rigid backing plate (stainless steel approximately 1.5 mm thick) is used to support the test specimen during the peel test. The dimensions of the backing plate are determined by the size of the specimen being tested as follows: the length of the plate is approximately 25 mm longer than the overall longitudinal length of the test specimen, and the width of the plate is approximately 10 mm wider than the lateral width of the test specimen measured at its widest point (excluding the wings).

[0162] A strip of microfiber material is used to simulate a wearer's underwear. The microfiber material used for this peel test is 92% polyester / 8% spandex, 130 gsm (or equivalent). This particular material can be obtained from Fruit of the Loom, Inc. microfiber shorts (largest size, available from any convenient source). Prior to testing, the material (or unused shorts) is washed once to remove any finishes as follows: The material (or unused shorts) is placed in a high efficiency front-loading washing machine (from any convenient source) with 48 g of TideFree and Gentle (or equivalent, but without additional additives such as odor protection, oxygen bleach, or fabric softeners). The washing machine is set on a "normal" cycle using warm water for washing and rinsing. After the wash cycle, the material (or unused shorts) is placed in a clothes dryer (mix-and-match with dry sensor, available from any convenient source). Set the temperature of the clothes dryer to "regular" and run the dryer until dry as indicated by the dryness sensor. After drying, equilibrate the material (or unused shorts) for at least 2 hours in a room controlled at a temperature of 23°C ± 3°C and a relative humidity of 50% ± 2%. Prepare a strip of microfiber material having a width equal to the widest part of the PFA pattern on the specimen with a length approximately 30 mm longer than twice the longitudinal length of the PFA pattern. The strip of microfiber material must be wide enough to cover the entire width of the PFA pattern and long enough to cover the entire length of the PFA pattern, overlapping itself completely and still with enough excess remaining to insert into the upper grip of the tensile tester. If the microfiber material is obtained from shorts, the length of the strip is cut in a direction perpendicular to the waistband and should not include any seams, waistband material, or gussets. Note which side of the material is intended to face the body (i.e., the inside of the shorts). The length of the strip of microfiber material must be long enough to cover the entire longitudinal length of the PFA pattern on the test specimen.However, if the strip of microfiber material obtained from the shorts is not long enough to overlap itself as described above, a strip of non-elastic standard cotton material (100% bleached cotton fabric, approximately 100 g / m2) may be used. 2 A strip of standard cotton (available from Testfabrics, Inc., West Pittston, PA, or equivalent) is used to supplement the length of the trailing end of the microfiber strip. A piece of standard cotton is cut to the same width as the microfiber strip and attached to the microfiber strip as follows: One of the longitudinal ends of the strip of standard cotton is placed over the trailing end of the microfiber strip, overlapping the trailing end of the microfiber by 25 mm. Ensure that the lateral edges of the microfiber and cotton strip are aligned, then use a piece of masking tape (1 inch wide, obtained from any convenient source) to secure the standard cotton strip to the strip of microfiber material. The masking tape is placed perpendicular to the longitudinal length of the material strip such that its width covers an equal portion of the microfiber and cotton strip. The masking tape is long enough to cover both sides of the overlapping strip. The masking tape is pressed firmly against both sides of the material strip to ensure proper fixation. A new strip of microfiber material is used for each test specimen.

[0163] A padded weight assembly is used to ensure that the strip of microfiber material adheres properly and evenly to the PFA. The weight assembly is rated at 26-27 g / cm with a base that has approximately the same length and width as the test specimen (width measured at the widest point on the test specimen excluding the wings). 2A pressure of 1000 psi must be applied to the weight assembly. The weight assembly is constructed as follows: A single layer of polyethylene film (0.02-0.04 mm thick; any convenient source) is laid flat on a bench surface. A piece of flexible insulating foam (Buna-N / PVC, 1 inch thick, 4.5 lb / ft 3 density; available from McMaster-Carr, Princeton, NJ, or equivalent), cut to the desired base size, is centered on top of the film. A metal weight with handle (same length and width as the desired base size) is then attached to the insulating foam using double-sided tape. The polyethylene film is then wrapped around the insulating foam and secured to the sides of the metal weight using clear tape.

[0164] To prepare the test specimen, first remove it from any wrapping material present, but leave the PFA protective covering (e.g., release paper) intact. If the wrapping material is a protective covering (e.g., PFA is attached directly to the wrapping material), then leave the wrapping material intact. If the specimen is folded, gently unfold it, smooth out any wrinkles, and determine which end of the specimen is intended to be the front end. If wings are present, unfold the wings. Without disturbing the PFA protective covering, determine the total length of the PFA pattern using a steel ruler (NIST certified) and remove the PFA. L Record to the nearest mm.

[0165] The specimen is attached to the backing plate as follows: The backing plate is placed horizontally on a flat rigid surface. The specimen is laterally centered on the backing plate with the body-facing side of the specimen facing down and the front longitudinal edge of the specimen aligned within 1 cm of the top longitudinal edge of the backing plate. The specimen is secured to the backing plate using single-sided tape (approximately 1 inch wide) as follows: The tape is positioned no closer than approximately 1 cm from any part of the PFA pattern and no tape is attached to any part of the PFA protective cover (e.g., release paper, wrapper). The front end of the specimen is secured to the backing plate by overlapping the end of the specimen with a strip of tape positioned approximately parallel to the lateral axis of the specimen. The specimen is now pulled to remove any wrinkles and the rear end of the specimen is secured to the backing plate by overlapping the end of the specimen with a strip of tape positioned approximately parallel to the lateral axis of the specimen. If the sample does not include wings, a strip of tape is used to secure the entire length of both lateral edges of the sample to the backing plate. If the sample includes wings, each wing is folded around a lateral edge of the backing plate and secured to the backside of the plate with tape. The remaining length of both lateral edges of the sample is then secured to the top side of the backing plate in a similar manner. The sample is secured in such a way that it is held taut without stretching in order to remain flat against the backing plate during the peel process. If the PFA covers the entire backsheet, tape is used only on the front and back edges of the sample so that the tape overlaps each end by about 1 cm or less.

[0166] After the specimen is secured to the backing plate and still resting on a flat, rigid surface with the PFA side of the specimen facing up, attach the prepared strip of microfiber material as follows: Remove the PFA protective cover from the specimen and determine whether the PFA pattern is longitudinally continuous (e.g., one or more stripes with no lateral spaces along its longitudinal length). Measure the entire longitudinal length of the PFA pattern and measure the PFA LRecord the measured value to the nearest 0.1 mm as the measured value. Center the strip of microfiber material laterally over the specimen (the inside of the shorts faces the specimen). Position the leading edge of the strip of microfiber material no more than 1 cm above the front edge of the PFA pattern. Align the longitudinal axis of the strip of microfiber material with the longitudinal axis of the specimen and secure it to the front edge of the PFA pattern. Continue to affix the strip of microfiber material to the remainder of the PFA pattern without wrinkling the microfiber material or the specimen. By design, an excess length of microfiber material (or standard cotton, if used to supplement the length of the microfiber) protrudes from the longitudinal trailing end of the specimen, referred to as the trailing end of the strip of microfiber material. Center and then place the prepared weight assembly over the specimen and on top of the attached strip of microfiber material. After 30±2 seconds have elapsed, remove the weight assembly and set it aside. The specimen must be pre-soaked for testing and analyzed within 1 minute after the weight assembly is removed.

[0167] Program the tensile tester for uniaxial extension at constant rate of extension and set the path length as follows: The gauge length is determined by the length of the backing plate and is set to approximately 10 mm greater than the length of the backing plate that is not in the lower grip. The gauge length is set using a calibrated ruler traceable to NIST or equivalent. Zero the crosshead and load cell. The path length is determined by the length of the PFA pattern PFA L Determined by PFA LThe distance between the backing plate and the test specimen is set at approximately 5 mm longer than the distance between the backing plate and the test specimen. Without disturbing the attached strip of microfiber material, insert approximately 10 mm of the bottom longitudinal edge of the backing plate (to which the trailing end of the test specimen is secured) into the grips of the bottom fixture of the tensile tester, ensuring that no part of the specimen is within the grips. The backing plate should be centered and parallel to the central tensile axis of the tensile tester. Now insert the trailing end of the microfiber material strip (or standard cotton, if used to make up the length of the microfiber material) into the grips of the top fixture of the tensile tester. Ensure that the strip of material is centered and parallel to the central tensile axis of the tensile tester. Adjust the amount of the strip of material in the top grip to ensure that there is no more than 0.1 N of tension to minimize slack in the microfiber material (and cotton, if used) at the trailing end of the PFA pattern and prevent premature delamination. Raise the crosshead at a rate of 1016 mm / min for the entire path length and collect force (N) and extension (mm) data at 50 Hz throughout the test. Return the crosshead to its original position. Create a graph of force (N) versus extension (mm).

[0168] For test specimens with a longitudinally continuous PFA pattern, the average force (F a ) is calculated, excluding all data points within the initial and final 1 cm of path length, and recorded to the nearest 0.01 N. The test is repeated in a similar manner for a total of five replicate test specimens. The average force (F a ) is calculated and reported to the nearest 0.01 N as the average force for the microfiber underwear.

[0169] For test samples with a PFA pattern that is not longitudinally continuous (e.g., one or more spaces along its longitudinal length), the resulting graph may consist of a series of peaks (bonded areas) and valleys (unbonded areas). For samples of this type, the maximum force at each peak along the path length is recorded to the nearest 0.01 N, excluding all data points within the initial and final 1 cm of the path length. The peak forces (F p ) is calculated and recorded to the nearest 0.01 N. The test is repeated in a similar manner for a total of five replicate test specimens. p ) is calculated and reported to the nearest 0.01 N as the average peak force for the microfiber underwear.

[0170] Adhesive Residue Test Method This test method is intended to simulate the in-use removal of an absorbent article adhered to a user's undergarment by PFA (panty fastening adhesive). After removal, the presence of residual adhesive on the undergarment is determined by visual inspection after enhancing the visibility of the residue with carbon black paper. All tests are performed in a conditioned room at 23°C ± 3°C and 50% ± 2% relative humidity, and test specimens are conditioned in this environment for at least 2 hours before testing.

[0171] To support the undergarment in a realistic manner during removal of the test specimen, a pair of cylinders are used to simulate the lower legs of a user. Each cylinder is 6 inches in diameter, approximately 18 inches tall, and constructed of high density polypropylene foam (e.g., AmazonBasics High Density Round Foam Rollers available from Amazon.com or equivalent). The cylinders are mounted approximately 6 inches apart on a rigid base large enough to prevent tilting and are secured to prevent rotation during use.

[0172] Women's size 8, white, 100% cotton shorts manufactured by Fruit of the Loom, Inc. (available from any convenient source) or equivalent are used as undergarments for this test. Prior to use, the cotton shorts are washed 30 times to remove any finishing agents as follows: The cotton shorts are placed in a high efficiency front-loading washing machine (available from any convenient source) along with 48g of TideFree and Gentle (or equivalent, but without additional additives such as odor protection, oxygen bleach, or fabric softeners). The washing machine is set on a "normal" cycle using hot water for washing and rinsing. After the wash cycle, the shorts are placed in a clothes dryer (mix-and-match with dry sensor, available from any convenient source). The clothes dryer temperature is set to "regular" and the dryer is run until dry as indicated by the dry sensor. This entire wash / dry cycle is repeated 30 times. After the 30th drying cycle, the cotton shorts are equilibrated in a room controlled at a temperature of 23° C.±3° C. and a relative humidity of 50%±2% for at least 2 hours.

[0173] The foam pad, rigid weight, and surface warmer are used to securely, properly, and evenly attach the test specimen to the cotton shorts. The foam pad is a piece of flexible insulating foam (Buna-N / PVC, 1 inch thick, 4.5 lbs / ft3 density; available from McMaster-Carr, Princeton, NJ, or equivalent) cut to size 69 mm x 305 mm. The foam pad is lightly wrapped in paper towels and secured with masking tape to prevent it from falling off when in contact with the white cotton shorts. The rigid, flat contact surface weight is 69 mm x 305 mm and has a handle attached. The rigid weight may be made of any material (e.g., stainless steel) to obtain a total mass (including handle) of 10.65 kg (the pressure exerted by the surface area of ​​the weight is 0.72 psi). The surface warmer must be capable of handling a set temperature of 37° C. and have a contact surface area large enough to accommodate the test specimen, pads, and rigid weights. A suitable surface warmer is a Premiere Slide Warme, model XH-2001 (available from Amazon.com) or equivalent.

[0174] Carbon black paper is used to facilitate the visualization of any adhesive residue left on the white cotton shorts. A suitable paper is Pelikan Carbon 1015G paper, size A4 (21 x 31 cm), or equivalent paper and size, available from any convenient source.

[0175] The test specimen is attached to the cotton shorts as follows: Place the foam pad lengthwise on the outside of the gusset / crotch area of ​​a pair of pre-washed / dried cotton shorts. Now, turn the shorts inside out to fit the gusset / crotch area over the foam pad, ensuring that the inside surface of the shorts is flat and wrinkle-free. Place the foam pad and shorts assembly on a flat, rigid surface with the inside of the gusset / crotch area of ​​the shorts facing up, noting which end is the front of the shorts. Remove the test specimen from any outer packaging and unfold to determine which end is intended to be the front end of the pad. If wings are present, cut them from the test specimen using scissors, taking care not to disturb the absorbent or PFA of the test specimen. Remove the protective cover from the PFA on the test specimen. The front fold of the test specimen is aligned with the front edge of the gusset on the shorts and centered laterally over the crotch area, then it is secured to the shorts by applying just enough pressure by hand. If the test specimen is not folded three times, the front third of the test specimen is aligned with the front edge of the gusset on the shorts and proceeds in the same manner. Now, with the right side of the shorts facing out, a foam pad is placed on the inside of the gusset / crotch area of ​​the shorts and centered over the attached test specimen. The surface warmer is set to 37°C and allowed to reach the temperature set point. The shorts, test specimen, and foam pad assembly is placed on the surface warmer with the warmer in contact with the outside of the gusset / crotch area of ​​the shorts. Now, a rigid 0.72 psi weight is centered over the foam pad and a 5 minute timer is started. After the 5 minutes have elapsed, the weight and foam pad are removed from the shorts and the shorts are removed from the surface warmer.

[0176] The test sample is removed from the shorts as follows: The shorts with the test sample attached are placed on foam cylinders representing the legs of the user. The shorts are turned upside down with one leg hole over one of the cylinders and then the other leg hole over the other cylinder. The front side of the shorts is firmly grasped near where the front end of the test sample was attached. Now, the front end of the test sample is firmly grasped. The front end of the test sample is pulled back and forth to remove the test sample from the shorts in a fast motion (approximately 200 mm / sec). The motion for removing the test sample from the shorts is intended to realistically mimic the removal of a pad from an undergarment.

[0177] The presence of adhesive residue is determined as follows: Remove the cotton shorts from the cylinder, being careful not to disturb the inside of the gusset where the test specimen was removed. Place the shorts on a flat rigid surface with the inside of the gusset / crotch area facing up. Place a piece of carbon black paper centered over the inside gusset of the shorts where the test specimen was removed. Now place a rigid 0.72 psi weight lengthwise over the paper, centered over the gusset, ensuring that the placement of the weight does not cause any movement of the carbon black paper on the shorts. Alternatively, in place of the rigid weight, apply manual pressure to the carbon black paper along the area where the test specimen was removed. After 15 seconds have elapsed, remove the weight and carbon black paper. The entire inside area of ​​the shorts where the test specimen was removed was visually observed to determine the presence of any adhesive residue (now black from the carbon paper). Any black dots, no matter how small, indicate residue and should be reported as such.

[0178] Dimensions and values ​​disclosed herein should not be understood as being strictly limited to the exact numerical values ​​recited. Instead, unless otherwise indicated, each such dimension is intended to mean both the recited value and a functionally equivalent range surrounding that value. For example, a dimension disclosed as "40 mm" is intended to mean "about 40 mm."

[0179] All documents cited herein, including any cross-referenced or related patents or patent applications, and any patent applications or patents to which this application claims priority or benefit, are incorporated herein by reference in their entirety, unless expressly stated to the contrary. The citation of any document shall not be deemed to be prior art to any invention disclosed or claimed herein, or to teach, suggest or disclose such invention, either alone or in combination with any other reference(s). Furthermore, to the extent that any meaning or definition of a term in this document conflicts with any meaning or definition of the same term in a document incorporated by reference, the meaning or definition assigned to that term in this document shall govern.

[0180] While particular embodiments of the present invention have been illustrated and described, it would be obvious to those skilled in the art that various other changes and modifications can be made without departing from the spirit and scope of the invention. It is therefore intended to cover in the appended claims all such changes and modifications that are within the scope of this invention.

Claims

1. 1. A disposable absorbent article comprising: a topsheet forming at least a portion of the wearer-facing surface of the absorbent article; a backsheet forming at least a portion of the garment-facing surface of the absorbent article; an absorbent core disposed between the topsheet and the backsheet; an adhesive for attaching the disposable absorbent article to an undergarment, the adhesive being disposed on the garment-facing surface, the absorbent article exhibiting a peel force of at least 1.0 N according to the Peel Force Test herein and leaving no residue on the undergarment according to the Adhesive Residue Test herein; 16. A disposable absorbent article comprising: a disposable absorbent article having a storage modulus-2 value of from 0.28 to 1.2 over a frequency range of 0.01 Hz to 1 Hz at 37° C., according to the Frequency Sweep-Oscillation Rheometry Test Method herein; a storage modulus-1 value of less than 85 kPa over a frequency range of 0.01 Hz to 1 Hz at 37° C., according to the Frequency Sweep-Oscillation Rheometry Test Method herein; a tan delta-2 value of less than or equal to 1.9 over a frequency range of 50-100 Hz at 37° C., according to the Frequency Sweep-Oscillation Rheometry Test Method herein; and a storage modulus-2 value of greater than 40 kPa over a frequency range of 50 Hz to 100 Hz at 37° C., according to the Frequency Sweep-Oscillation Rheometry Test Method herein, wherein said storage modulus-2 value is greater than the storage modulus-1 value.

2. The disposable absorbent article of claim 1, wherein said absorbent article exhibits a peel force of from 1.0N to about 5.0N.

3. 3. The absorbent article of claim 1 or 2, wherein the adhesive is acrylate-based or comprises a mixture of ethylene vinyl acetate and styrene block copolymers.

4. The absorbent article of any one of claims 1 to 3, wherein said adhesive exhibits a tan delta-2 of 0.25 to 1.9 in the frequency range of 50 Hz to 100 Hz at 37°C according to the Frequency Sweep-Oscillatory Rheometry test method herein.

5. The adhesive has a thermal conductivity of about 10 mJ / m2 according to the measurement method described herein. 2 The absorbent article of any one of claims 1 to 4, exhibiting a surface energy of up to about 25 mJ / m2.

6. The absorbent article of any one of claims 1 to 5, wherein said adhesive exhibits a polar component of surface energy of between 1 percent and 10 percent according to the measurements herein.

7. 7. The absorbent article of any one of claims 1 to 6, wherein said adhesive has a Storage Modulus-1 value of from 1 kPa to 84 kPa at frequencies of 0.01 to 1 Hz at 37°C according to the Frequency Sweep-Oscillatory Rheometry test method herein.

8. The absorbent article of any one of claims 1 to 7, wherein said adhesive exhibits a tan δ-2 value of 0.25 to 1.9 at frequencies of 50 to 100 Hz at 37°C according to the Frequency Sweep-Oscillatory Rheometry test method herein.

9. The absorbent article of any one of claims 1 to 8, wherein the adhesive exhibits a relaxation time of 100 seconds or less at a temperature of 37°C according to the measurement method herein.

10. The absorbent article of any one of claims 1 to 9, wherein said adhesive exhibits a yield stress of 32 kPa or greater at 37°C as determined by the Elongation Test Method herein.

11. The adhesive of any one of claims 1 to 10, wherein the adhesive exhibits a yield stress of from 32 kPa to 100 kPa.

Citation Information

Patent Citations

  • Sanitary napkins with adhesive that comes into contact with the human body

    JP2001517488A

  • Disposable absorbent article with improved retention performance of hydrophobic materials, especially microfiber materials

    JP2007527780A

  • Pressure-sensitive hot melt adhesive composition including propylene thermoplastic elastomer and articles including the same

    US20140371703A1

  • Adhesive and Use for Attachment to Microfiber Garments

    US20150034244A1

  • Adhesive and Use for Attachment to Microfiber Garments

    US20150038938A1